Government of Sierra Leone Education Data Hub: A User Research Report - Freiermuth, Sophie; Bedoui, Claire; Middleton, Emily; Taddese, Abeba (EdTech Hub, 2020)
Report on the Government of Sierra Leone Education Data Hub
previousDOI: 10.5281/zenodo.3960140 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3960140 10.53832/edtechhub.0027 2339240:6E8ZDLYB 2339240:Z28GJH3E 2405685:6TJ92NFH 2405685:6XEEQHVU 2405685:8CB5PTUQ 2405685:EERE25UX 2405685:FQKKVE4W 2405685:K4DEZSCM 2405685:L4ULUSCB 2405685:NTMUHEW9 2405685:S4VEIC5W 2405685:W7SY73AT
Keywords: C:Sierra Leone; ES:Educational data; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

EdTech in Sierra Leone: A Rapid Scan - Mullan, Joel; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and in this case, in Sierra Leone. This report is based primarily on desk research, with quality assurance provided by a country expert.
previousshortDOI: 10/ghgnd3 previousDOI: 10.5281/zenodo.3903213 shortDOI: 10/ghgnd3 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3903213 10.5281/zenodo.3903213 10.53832/edtechhub.0038 10/ghgnd3 2339240:4GMNADXW 2339240:NJVI79X2 2339240:VJKBU72Y 2405685:C5MWWQI2 2405685:D25NXEFY 2405685:NNCCIL5M 2405685:RHJ9EDQH 4656463:K7AIYRDP
Keywords: C:Sierra Leone; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Sierra Leone : Economic Development Documents-National Development Plan, 2019-23 - International Monetary Fund. African Dept. (2019)
The Government of Sierra Leone’s new Medium-term National Development Plan (MTNDP) 2019–2023 has been founded on a strong political commitment to deliver devel-opment results that would improve the welfare of Sierra Leone’s citizens. The plan charts a clear path towards 2023 en route to the goal of achieving middle-income status by 2039 through inclusive growth that is sustainable and leaves no one behind. For the next five years, the Free Quality School Education Programme is the government’s flagship programme to provide a solid base to enhance human capital development and to facilitate the transformation of the economy.
9781498324960/1934-7685 KerkoCite.ItemAlsoKnownAs: 2405685:DJ4XD4HB

Sierra Leone Multiple Indicator Cluster Survey 2017 - Statistics Sierra Leone (Statistics Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:7794TCGJ 2405685:N9SALPUS

The Sierra Leone Teachers Union: Labor in a Post-Conflict Society - Amman, John; O'Donnell, James (WorkingUSA, 2011)
The Sierra Leone Teachers Union (SLTU) has long played an important role in the country's education system and its labor movement. With more than 30,000 members, the SLTU is the largest and perhaps the most powerful union in Sierra Leone today. Nonetheless, the union struggles with challenges unheard of in developed countries. It represents teachers in an education system that was ravished by its eleven-year civil war (1991 to 2002). Not only are working conditions extremely difficult for teachers (classroom overcrowding, lack of educational materials, low pay, and often late pay), the union must negotiate union agreements with the Ministry of Education, which itself has no direct influence on the nation's coffers. Sierra Leone's Ministry of Finance and more importantly, the International Monetary Fund set policies that directly impact the quality of Sierra Leone's education system and its teachers.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1743-4580.2011.00320.x KerkoCite.ItemAlsoKnownAs: 10.1111/j.1743-4580.2011.00320.x 2405685:K8W49AUJ

Outputs Register: The Impact of GIS-Supported Teacher Allocation in Sierra Leone - Haßler, Björn; McBurnie, Chris; Beoku-Betts, Iman; Frazer, Madleen Madina (EdTech Hub, 2023)
EdTech Hub, Fab Inc, and the Education Workforce Initiative have produced the outputs listed in this document as part of the EdTech Hub-commissioned research project on ‘GIS-supported teacher allocation in Sierra Leone’. This research project began in January 2022. This document lists all outputs produced under this project. All outputs are available to the public via the EdTech Hub Evidence Library. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6396199 10.5281/zenodo.6472492 10.53832/edtechhub.0089 10.53832/edtechhub.0163 10.53832/edtechhub.0164 2129771:3J4TNGDZ 2339240:QAKR5YM8 2405685:9XJGEX5Z 2405685:NNBEHF4D 2405685:WXBISTFE
Keywords: Author:OpenDevEd; HLR3; _C:Sierra Leone SLE; _r:AddedByZotZen

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
oldDOI: 10.5281/zenodo.6498098 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6498098 10.5281/zenodo.7716253 10.53832/edtechhub.0082 10.53832/edtechhub.0170 2339240:7MIS2I79 2405685:MS3CKE8G 2405685:T3F6DCHP 2405685:UJWVTSCK
Keywords: _r:AddedByZotZen

Sierra Leone : Poverty Reduction Strategy Paper-Progress Report (2005-2007) - International Monetary Fund (2008)
This report describes the progress made in implementing the Poverty Reduction Strategy Paper for Sierra Leone covering the period 2005–07. Efforts to reform the public sector were not successful. Management and Functional Reviews were conducted for several ministries, departments, and agencies but the recommendations were not implemented. A Senior Executive Service program was also developed but government and development partners could not agree on an implementation strategy and therefore the funds required for implementation were not provided.
KerkoCite.ItemAlsoKnownAs: 2405685:WDN7YDZH

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6817992 10.53832/edtechhub.0171 2405685:KAAC2B78
Keywords: _r:AddedByZotZen

School-to-School Mobility Patterns and Retention Rates of Payroll Teachers in Sierra Leone - Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alisdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone. Recent studies from this series have shown that being put on the government payroll can incentivise teachers to relocate to remote areas of the country. There is a concern, however, that being put on the payroll does not necessarily ensure the retention of teachers in these areas and that teachers will soon move to locations they consider more favourable. As there is no data on teacher mobility patterns and schools’ teacher retention rates, policies tend to be based on anecdotal evidence. This paper aims to fill this evidence gap by exploring teachers’ school-to-school mobility trends and retention rates using the Annual School Census (ASC) data from 2015 to 2021. Using data on teachers’ individual characteristics, as well as geospatial location data of each school, the paper explores whether mobility patterns vary by teachers’ gender or qualifications and whether the teaching workforce is urbanising. While studies have looked at teacher retention, this study is the first in a low-income country to use school census data to create a panel dataset to study teachers’ movements and school retention rates over time. Keywords: teacher mobility; teacher retention rates; mobility patterns; teacher deployment; Sierra Leone; education An output of the EdTech Hub https://edtechhub.org
ZenodoArchiveID: 7421516 ZenodoArchiveConcept: 7421515 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7421516 10.53832/edtechhub.0143 2405685:DE7XUSMJ 2405685:IWFRG7US 2486141:MQHWRFUH
Keywords: _r:AddedByZotZen

Teacher Deployment in Sierra Leone: Lessons learnt and going forward - Beoku-Betts, Iman (EdTech Hub, 2023)
This report provides an overview of the teacher deployment process in Sierra Leone prior to and including 2022. Through interviews with key stakeholders in the Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC), we look at lessons learnt from the deployment process and next steps for how teacher deployment can be implemented. Although there are a number of volunteer teachers in Sierra Leone, the TSC are aiming to increase the number of qualified teachers on the government payroll as well as retaining teachers in rural areas. It was noted that teachers from rural areas being put on the government payroll and deployed to rural schools are better placed to teach in rural schools than teachers moving from urban to rural areas. Hpwever, it is still challenging to find qualified teachers in these rural areas. The TSC want to look at how they can target teachers to take up rural positions, either through distance learning to gain the right qualifications or working with teacher training institutions (TTIs) to prioritise schools in rural areas for placement. Overall, the TSC want to use data as the basis for decision-making on deploying teachers equitably. Keywords Teacher deployment; teacher training; unqualified teachers; volunteer teachers; rural schools; data for decision-making An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521062 ZenodoArchiveConcept: 7521061 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521062 10.53832/edtechhub.0145 2405685:M3D6NGR4 2405685:WVRHTVIZ 2486141:V94NMZIU
Keywords: _r:AddedByZotZen

School Leaders’ Preferences on School Location in Sierra Leone: An individual and school-level study - Espinoza-Revollo, Patricia; Ramirez, Ana; Atherton, Paul; Mackintosh, Alasdair (EdTech Hub, 2022)
Attracting qualified teachers to remote areas is a challenge in Sierra Leone. The pupil-to-qualified-teacher ratio in rural areas is 76:1, rising to 83:1 for schools located more than 15 km away from urban centres — well above the national target of 40:1. As equitable teacher deployment is crucial to ensure high-quality education, the Teaching Service Commission (TSC) aims to increase the deployment of qualified teachers to the most remote areas of the country. This paper describes a quantitative survey of school leaders’ perceptions of what shapes school location preferences and what factors need to be in place (i.e., incentives) to address the imbalanced distribution of qualified teachers in the country. We used data from a text message survey sent to school leaders around the country. This paper accompanies a qualitative inquiry on the same topic: What Matters Most for Teacher Deployment? A case study on teacher school choice preferences in Sierra Leone. Together with the qualitative study, our findings aim to address a gap in empirical evidence on teacher school preferences in Sierra Leone and contribute to a growing literature on teachers’ preferences in low- and middle-income countries. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6958056 10.53832/edtechhub.0106 2405685:MFH269TU
Keywords: _r:AddedByZotZen

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13256782 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1053 ZenodoArchiveConcept: 13256781
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone invests $1.5 million to bring education innovation to schools for better learning outcomes - Sierra Leone Education Innovation Challenge (2019)
A national education dashboard released last month by Sierra Leone’s agency for technology and innovation and the Ministry of Basic and Senior Secondary Education (MBSSE) showed that schools and studentsRead More
Library Catalog: www.dsti.gov.sl EdTechHub.ItemAlsoKnownAs: 2405685:XUALMEQ5

Investigating the Activity Levels of School Quality Assurance Officers in Sierra Leone - Beoku-Betts, Iman; Leh Wi Lan (EdTech Hub, 2023)
Since the launch of the Free Quality School Education (FQSE) Programme in 2018, the Sierra Leone Ministry of Basic and Senior Secondary Education (MBSSE) has prioritised the use of data for decision-making across several education reform programmes. Part of this vision has been to build systems to measure school quality through School Quality Assurance Officers (SQAOs) using data collection and feedback. This system includes using tools for teacher management, lesson observations, school improvement, and attendance monitoring. This report presents findings from qualitative research conducted in three districts in Sierra Leone. The aim is to provide the MBSSE and other partners with insights to understand the variation in and what is needed to maximise SQAO activity levels, increase principal engagement with digital tools, and support and promote quality visits to schools. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521375 ZenodoArchiveConcept: 7521374 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521375 10.53832/edtechhub.0154 2405685:AHVWDNGT
Keywords: _r:AddedByZotZen

Sierra Leone turns to technology and analytics to put quality back into education - Directorate of Science, Technology & Innovation (Sierra Leone) (2019)
Today, an estimated 2 million students return to school for the second year of the Free Quality School Education (FQSE) Program. The Government of Sierra Leone commits 21% of theRead More
Library Catalog: www.dsti.gov.sl KerkoCite.ItemAlsoKnownAs: 2405685:Z3DPRDU6

‘Without Education You Can Never Become President’: Teenage Pregnancy and Pseudo-empowerment in Post-Ebola Sierra Leone - Menzel, Anne (Journal of Intervention and Statebuilding, 2019)
This article analyses the emergence of ‘teenage pregnancy’ as a new policy focus in post-Ebola Sierra Leone and explores how Sierra Leoneans interpret the problem of ‘teenage pregnancy’. I argue that the new policy focus is not indicative of changing or new problems. Rather, ‘teenage pregnancy’ has created opportunities for donors and the Government of Sierra Leone to continue cooperation in gender politics. At the same time, Sierra Leoneans are clearly concerned about ‘teenage pregnancy’, and many agree with sensitization campaigns that responsibilize young women and girls while downplaying structural factors that render them vulnerable to arrangements involving transactional sex.
Publisher: Routledge _eprint: https://doi.org/10.1080/17502977.2019.1612992 KerkoCite.ItemAlsoKnownAs: 10.1080/17502977.2019.1612992 2405685:MKDQ3K53
Keywords: Sierra Leone; aid and development; gender politics; neoliberalism; sexual violence; teenage pregnancy

Does living in a community with more educated mothers enhance children's school attendance? Evidence from Sierra Leone - Kamanda, Mamusu; Madise, Nyovani; Schnepf, Sylke (International Journal of Educational Development, 2016)
In Sierra Leone girls are 23.4% less likely to attend secondary education than boys. This difference between sexes increases the gender gap in educational attainment since women's education is positively associated with children's educational wellbeing. This paper investigates the relationship between children's school attendance, their mothers’ level of education, as well as the overall level of women's education at the community level in Sierra Leone using multilevel statistical modelling techniques and the country's 2008 Demographic and Health Survey data. The findings suggest that, regardless of a child's own mother's education, an increase in the proportion of mothers with secondary or higher education in a community by 10% improves the probability of attending junior secondary school significantly by 8%; a 50% increase improves the likelihood of attending school by 45%. There was no significant relationship between the proportion of better educated mothers in a community and primary school attendance. However, relative to children whose mothers had no formal education, children whose mothers had attained primary, secondary or higher education were 7%, 14% and 22% more likely to attend primary school respectively. Future policies should seek to promote girls’ education at post-primary education and develop community based programmes to enable the diffusion and transmission of educational messages.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2015.09.008 2405685:YPUYEULY
Keywords: Girls’ education; Mothers’ education; School attendance; Sierra Leone

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

Sierra Leone series: Freetown Teachers College and its multimodal approach to teacher professional development - McBurnie, Chris; Moriba, Sambo; Brainard, Prince (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week two, we connected with Dr Samba Moriba and Prince Brainard from Freetown Teachers…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4584801 2339240:F47KL5P7 2339240:VJ2SHXTR 2405685:DJHAECID 2405685:JV4FPSJW
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodoETH; dode_eth-src-eth

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707910 2405685:7HCBSU4P
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Sierra Leone series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health. - Tahi (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week one, we connected with Abdulai Swaray and Bai Kamara from the Pikin-to-Pikin Movement.…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707926 2405685:FB4FWFP9
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Sierra Leone Demographic and Health Survey 2008 - Statistics Sierra Leone (Ministry of Health and Sanitation, 2009)
KerkoCite.ItemAlsoKnownAs: 2405685:XJLGGACD

Understanding Sierra Leonean and Liberian teachers’ views on discussing past wars in their classrooms - Shepler, Susan; Williams, James H. (Comparative Education, 2017)
Various curricular and textbook initiatives exist to aid in the national processes of coming to terms with past violence, often serving the political goals of the victors, sometimes supported by international transitional justice institutions. Sierra Leone and Liberia each experienced a devastating civil war during the 1990s and into the 2000s, and each is struggling to rebuild shattered education systems. In addition, each country has experienced a set of post-conflict transitional justice initiatives: Truth and Reconciliation Commissions in each, and a Special Court for Sierra Leone. Although their respective ministries of education have attempted to address peace education through UNICEF-sponsored curriculum revision processes, those efforts have not yet reached the majority of serving teachers, so a discussion of teachers’ actual practices is vital. This article uses interviews with teachers in rural and urban Sierra Leone and Liberia to discuss whether and how teachers talk about past war in their classrooms; whether they think it is important to discuss past conflicts, and if so, why; and what kind of curricular support would help them better teach about the wars. The article discusses how and why teachers embrace or subvert official efforts through their classroom practices, and compares the Sierra Leone and Liberia contexts and results. This research will help us to understand teachers’ own perspectives on addressing past conflict in their classrooms, and perhaps help policy-makers better implement their peace education initiatives.
Publisher: Routledge _eprint: https://doi.org/10.1080/03050068.2017.1338641 KerkoCite.ItemAlsoKnownAs: 10.1080/03050068.2017.1338641 2405685:9FVX5LB3
Keywords: Education; Liberia; Sierra Leone; teachers; teaching about conflict; transitional justice

Sierra Leone: Price for 1GB mobile data 2023 - Galal, Saifaddin (Statista, 2024)
One gigabyte of mobile internet in Sierra Leone cost, on average, 0.67 U.S.
KerkoCite.ItemAlsoKnownAs: 2339240:BB8CTHX7 2405685:QH66APIU

EdTech in Sierra Leone: Reimagining education for continuous learning and teaching - Sengeh, David Moinina (Global Partnership for Education, 2021)
Read how the government of Sierra Leone is using technology to address the profound ongoing teaching and learning crisis, and deliver inclusive, quality education.
KerkoCite.ItemAlsoKnownAs: 2339240:IH3IUFW4 2405685:PDME63H4

Sierra Leone Multiple Indicator Cluster Survey 2017, survey findings report - Statistics Sierra Leone (Statistics Sierra Leone, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:SMX372XG 2405685:EP6QPCSW

Sierra Leone: Historic bill to end child marriage passed - sustained efforts to raise community awareness must now follow - Amnesty International (Amnesty International, 2024)
Reacting to the signing into law of the Prohibition of Child Marriage Act 2024 on 2 July by President Julius Maada Bio, Samira Daoud, Amnesty International Regional Director for West and Central Africa, said: “We welcome this historic law banning child marriage in Sierra Leone. This legislation, in criminalizing marriage for anyone under the age […]
KerkoCite.ItemAlsoKnownAs: 2339240:SPWEDJ65 2405685:Z8IWGGN8

Teacher Retention and Mobility in Sierra Leone: What factors motivate teachers to stay at or leave schools? - Lurvink, Anne-Fleur; Mansaray, Kabiru; Kamara, Josephine; Khanu, Alimamy James; Cameron, Emma; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
The current study is the third in a series of research studies, which aim to generate evidence that can support the MBSSE and TSC with their teacher allocation and deployment strategy. Our first study investigated teacher preferences for school choice and uncovered important considerations for teacher deployment. Following this, we investigated mobility patterns for teachers who are on the government payroll, and payroll teacher retention rates. The latter study helped us understand where teachers move to when they change schools, and also helped us identify areas with high (hot spots) and low retention rates (cold spots). The current study is explanatory in nature and aims to understand why teachers stay at or leave their schools. Keyword: teacher allocation; teacher retention; teacher mobility; Sierra Leone An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7966434 ZenodoArchiveConcept: 7966433 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7966434 10.53832/edtechhub.0168 2405685:CQ8JNCH8
Keywords: _r:AddedByZotZen

Education service transformation in Sierra Leone: Where policy meets the people | Blog | Global Partnership for Education - Sengeh, David Moinina (2020)
As GPE prepares to launch a new five-year strategic plan responding to partner countries’ demands for transformative change, GPE Board Member and Minister of Basic and Senior Secondary Education David Moinina Sengeh shares learnings from his first year of office on what transforming education means to the people of Sierra Leone.
KerkoCite.ItemAlsoKnownAs: 2339240:DE8NBSA7 2405685:TJT9ZI8V

Sierra Leone Medium Term National Development Plan (Volume 1) - Ministry of Planning and Economic Development (Sierra Leone) (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:CZE9NFVC

Sierra Leone designs online portal to take long wait out of teacher recruitment - Directorate of Science, Technology & Innovation (Sierra Leone) (2019)
A new teacher recruitment portal developed at the Directorate of Science, Technology, and Innovation (DSTI) will make it easier and faster for education administrators to hire teachers, and allocate teachersRead More
Library Catalog: www.dsti.gov.sl KerkoCite.ItemAlsoKnownAs: 2405685:UWP4N7FT

Leh Wi Lan: Improving The Quality Of Secondary Education In Sierra Leone - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:Y7RFFB9I

Transforming education service delivery in Sierra Leone: from evidence to action - Sengeh, David Moinina; May-Wilson, Hannah (Global Partnership for Education, 2020)
Sierra Leone’s education system has been plagued by events that have challenged the effective delivery of high-quality education for every child for nearly three decades. But thanks to a program launched in 2018, the government is achieving greater access, quality, and equity for children by removing financial barriers to school enrollment and improving teaching and learning outcomes.
KerkoCite.ItemAlsoKnownAs: 2339240:BFQBRATB 2405685:PS758V8V

National Digital Learning Strategy for the Sierra Leone Ministry of Basic and Senior Secondary Education & Teaching Service Commission 2025–2030 - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2025)
Sierra Leone launches first-ever National Digital Learning Strategy The Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC) are pleased to announce the launch of Sierra Leone’s first-ever National Digital Learning Strategy (NDLS) — a groundbreaking framework aimed at leveraging educational technology to improve teaching and learning in Sierra Leone. Developed through a collaborative and consultative process with representatives from the MBSSE, TSC, Ministry of Tertiary and Higher Education (MTHE), Presidential Delivery Unit (PDU), and Ministry of Communications, Technology, and Innovation (MoCTI) and shaped by insights from students, teachers, district leaders and officials, the NDLS outlines key priorities related to addressing the digital divide in Sierra Leone; improving teachers’ digital capabilities; strengthening learners’ access to technology; improving access to localized content, and improving coordination mechanisms between all EdTech stakeholders. EdTech Hub is a proud partner of this work alongside the UK Foreign, Commonwealth and Development Office (FCDO), UNICEF, the World Bank, and other collaborators. This collaboration included technical guidance and support throughout the process. The NDLS represents a collective commitment to transforming education and building future-ready learners and educators.
KerkoCite.ItemAlsoKnownAs: 2405685:WVVB6PCG

Remote Supervision Options for School Quality Assurance Officers: Recommendations for a cost-effective and rapid develop-and-test process - Beoku-Betts, Iman; Ampofo, Rudolph; Haßler, Björn (EdTech Hub, 2024)
The Sierra Leone Secondary Education Improvement Programme II (SSEIP II) is a five-year programme funded by the UK Foreign, Commonwealth and Development Office (FCDO) to support the Ministry of Basic and Senior Secondary Education (MBSSE) to improve learning outcomes for students at secondary level and to increase the enrolment, retention and well-being of girls and children with disabilities in school. Part of the programme includes exploring the use of different digital tools for School Quality Assurance Officers (SQAOs), including tools for remote visits. In December 2022, the EdTech Hub collaborated with the Government of Sierra Leone and implementing partners of the Leh Wi Lan programme (continued under SSEIP II) to better understand what factors affect the variability in the activity levels of SQAOs and the level of engagement with digital tools by school principals. Based on the findings of this research, the SSEIP II project will look at supporting the MBSSE to formalise remote supervision options for the SQAOs, particularly for those with remote clusters. As part of this work, this report focuses on recommendations for how SQAOs can conduct remote school visits, particularly for schools in hard-to-reach areas.An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10354009 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1002 ZenodoArchiveConcept: 10354008
Keywords: _r:AddedByMyEducationEvidence

Worldreader | Sierra Leone - Worldreader (2020)
Worldreader brings digital reading to schools in Sierra Leone in partnership with the Klintworth Family Foundation.
Library Catalog: www.worldreader.org EdTechHub.ItemAlsoKnownAs: 2405685:FHAMLZRG

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
2339240:7FA4YDWJ 2339240:YBKKN8XE KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5498054 10.5281/zenodo.5498054 2339240:3H4M8YJ8 2339240:5S4BZY48 2339240:SRWI5WQJ 2405685:BCFK4Q23 2405685:JR65CZU2 2405685:JTKTA5X5 2405685:VQ3F9NQ7 2405685:ZLATZSGU 4656463:RIFY2UNL
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Sierra Leone 2015 population and housing census: Thematic report on poverty and durables - Statistics Sierra Leone (Statistics Sierra Leone, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:YKBEPH82 2405685:MPV2GIIW

Government–donor relations in Sierra Leone: Who is in the driving seat? - Harris, David; Conteh, Felix Marco (The Journal of Modern African Studies, 2020)
Since the cessation of conflict in 2002, Sierra Leone has experienced extraordinary levels of involvement from Western donors. Paradoxically, while relationships are often portrayed on the ground as strong with significant donor influence, our research shows considerable fluidity in individual and institutional relationships. The article disaggregates donor–government relations at various levels over a short but crucial period, 2010–16, asking in each case who occupies the driving seat. In so doing, the article interrogates the concept of ‘extraversion’, investigating to what extent government – and indeed donors – has space in which to manoeuvre and how and why government and donors act as they do in this space. The period 2010–16 is of particular interest due to extreme iron ore price volatility and the Ebola epidemic of 2014–15. The article adds much-needed critique and empirical evidence to the debate on donor influence and ‘extraversion’.
KerkoCite.ItemAlsoKnownAs: 10.1017/S0022278X19000569 2339240:6BGFKPNW 2405685:ZJ7VE4Y6

Sierra Leone invests $1.5 million to bring education innovation to schools for better learning outcomes - DSTI Media (Directorate of Science, Technology and Innovation, 2019)
A national education dashboard released last month by Sierra Leone’s agency for technology and innovation and the Ministry of Basic and Senior Secondary Education (MBSSE) showed that schools and studentsRead More
KerkoCite.ItemAlsoKnownAs: 2405685:B6TMDRUY

Redesigning an education project for child friendly radio: a multisectoral collaboration to promote children’s health, education, and human rights after a humanitarian crisis in Sierra Leone - Barnett, Sarah; van Dijk, Jetske; Swaray, Abdulai; Amara, Tamba; Young, Patricia (BMJ, 2018)
Sarah Barnett and colleagues describe how an educational project was rapidly adapted into a radio education programme after the 2014 Ebola epidemic in Sierra Leone
shortDOI: 10/ggqvr7 KerkoCite.ItemAlsoKnownAs: 10.1136/bmj.k4667 10/ggqvr7 2339240:6IXLT92N 2405685:6Z36JH5J 2405685:S35X3HD9

Sierra Leone’s Medium-Term National Development Plan 2019-2023: Education for Development. - Government of Sierra Leone (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:RPKBXC8H 2405685:XNWLCKWJ

Digital School Census in 10 Weeks? How it was done in Sierra Leone - Namit, Kariba; Mai, Thanh Thi (World Bank Blogs, 2019)
Note: This blog is specifically about Sierra Leone’s successful transition to a digital school census but has broader implications for other countries who plan to adopt digital tools at a wider scale to collect data and monitor education and healthcare facilities in their countries. In April of last year, the new Minister of Finance of Sierra Leone approached the World Bank with a strong commitment to prioritize education and an intriguing request.
Library Catalog: blogs.worldbank.org KerkoCite.ItemAlsoKnownAs: 2339240:PP5768J6 2339240:TGTJZWCC 2405685:EPMH5GMB 2405685:EY9VEBRN 2405685:KXNLTUXL 2405685:NUSFD2XU 2405685:PLIT3YBG 2405685:TIEFATQQ 4803016:S4RTD2LL

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694591 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1014 ZenodoArchiveConcept: 10694590
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone 2015 Population and Housing Census: Thematic Report on Disability - Kabia, Francis; Tarawally, Umaru (Statistics Sierra Leone, 2017)
KerkoCite.ItemAlsoKnownAs: 2405685:BI8HMKXI

Sierra Leone: Education Country Status Report: An analysis for further improving the quality, equity and efficiency of the education system in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2013)
KerkoCite.ItemAlsoKnownAs: 2405685:FWX5GT4H

National ICT Policy of Sierra Leone - Ministry of Information and Communications (Government of Sierra Leone, 2009)
KerkoCite.ItemAlsoKnownAs: 2339240:GI5IQFVY 2405685:BVA56A3C
Keywords: ⛔ No DOI found

Education Sector Plan, 2018-2020: Getting It Right – Service Delivery, Integrity and Learning in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:AIISD4KD 2405685:DFHS5ZVL

Making strides to make digital literacy facilities accessible to children across Sierra Leone - Mason, Harriet (UNICEF Sierra Leone, 2022)
Making strides to make digital literacy facilities accessible to children across Sierra Leone
KerkoCite.ItemAlsoKnownAs: 2339240:YWVSPC2X 2405685:7WZT7QGS

Building the Next Generation of Girls (and Boys) in Technology in Sierra Leone - Abakah, Julian; Mason, Harriet (UNICEF Sierra Leone, 2023)
Building the next generation of Girls (and boys) in Technology in Sierra Leone
KerkoCite.ItemAlsoKnownAs: 2339240:SNRGEUMK 2405685:ADDZMLVR

Sierra Leone Demographic and Health Survey 2019 - Statistics Sierra Leone (The DHS Program, 2020)
ICF
KerkoCite.ItemAlsoKnownAs: 2339240:J5MWI9UW 2405685:MEUW6R9C 2405685:MZXSNEV5

The teacher salary system in Sierra Leone - Turrent, Victoria (2012)
KerkoCite.ItemAlsoKnownAs: 2129771:57MI994B 2129771:EDZ7UPYF 2339240:HPKYUKLY 2339240:K8K3HH88 2405685:JYDRFRHV 2405685:LR6N966K 2405685:YMKMBLNW 2486141:5RFTC82M 4556019:2UB9U5R4
Keywords: C:Sierra Leone; _C:Sierra Leone SLE; ⛔ No DOI found

The Agenda for Prosperity: Road to Middle Income Status - Government of Sierra Leone (2013)
KerkoCite.ItemAlsoKnownAs: 2339240:FHMH4G7H 2405685:7DIVY6PP
Keywords: ⛔ No DOI found

Sierra Leone National Innovation and Digital Strategy (2019-2029). Digitization for all: Identity, Economy, and Governance - Directorate of Science, Technology & Innovation (Government of Sierra Leone, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:Q6QR6YET 2339240:Q8HXYPXT 2339240:ZAK6UTWJ 2405685:65CSGZUZ 2405685:ALD9DQ6P 2405685:GWCHFY72 2405685:XG7MKFV5

Orange Education Portal - Orange Sierra Leone (2020)
Library Catalog: www.orange.sl KerkoCite.ItemAlsoKnownAs: 2405685:YV3WDQAQ

Sierra Leone Education Sector Plan: Transforming learning for all 2022–2026 - Government of Sierra Leone (2022)
KerkoCite.ItemAlsoKnownAs: 2405685:8FE32XB4 2486141:8HN4J7TQ

Sierra Leone Public Expenditure Review 2021: Fiscal Policy for a Sustainable Recovery - World Bank (World Bank, 2021)
This Fiscal and Debt Sustainability Note, the first module of a programmatic multisectoral Public Expenditure Review (PER), reviews the recent macro-fiscal challenges, analyzes their causes and consequences and provide policy options for enhancing the conduct of fiscal and PFM policies in the country. The first part of this module draws on the Boost database to provide a comprehensive overview of the budget covering both revenues and expenditures. It analyzes the composition of the budget (based on economic and functional classifications) and discusses the most critical PFM issues the country faces. It also assesses budget execution and the efficiency of public expenditure. The second part of the module focuses on fiscal risks and their implications for medium-term fiscal and debt sustainability. It examines the recent evolution of public debt, its main drivers and relationship to economic growth. It describes recent reforms to address fiscal and debt vulnerabilities and how these reforms have been affected by the global pandemic. It also analyzes the main fiscal risks with a focus on those stemming from State-Own Enterprises (SOEs), local councils, litigations, natural disasters, and health crises. This part uses simulations to analyze the most likely evolution of the public debt path over the next 20 years under alternative risk scenarios. Finally, the module proposes practical and actionable policy options to help improve the macro-fiscal environment over the short term and preserve debt sustainability over the medium term.
Accepted: 2021-06-29T15:28:44Z KerkoCite.ItemAlsoKnownAs: 2339240:QWRVJMBE 2405685:KDMZ7CXM
Keywords: Debt Sustainability; Fiscal Policy; Fiscal Sustainability; Public Debt; Public Expenditure; Public Financial Management; Public Investment Management; State-Owned Enterprises

Universal Access Development Fund | Home - Universal Access Development Fund (Sierra Leone) (2020)
EdTechHub.ItemAlsoKnownAs: 2405685:FNIEIP9B

Schools ICT project - Universal Access Development Fund (Sierra Leone) (2020)
Library Catalog: uadf.gov.sl EdTechHub.ItemAlsoKnownAs: 2405685:UXGCRKTI

Out-Of-School Children Study Sierra Leone - Government of Sierra Leone; Irish Aid; UNICEF (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:FUGDDXTR 2405685:8IWQ2ZSL

Scientists at DSTI go the extra mile to make it easier for children to get to school - Directorate of Science, Technology & Innovation (Sierra Leone) (2020)
Mike Fabrikant, a software developer from Washington D.C., is embedded within the data science team at the Directorate of Science, Technology, and Innovation (DSTI) to support systems delivery. His workRead More
Library Catalog: www.dsti.gov.sl KerkoCite.ItemAlsoKnownAs: 2405685:9K5VWY7C

DSTI | Home - Directorate of Science, Technology & Innovation (Sierra Leone) (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:T64PHUNV

Ministry of Information and Communications | Home - Ministry of Information and Communications (Sierra Leone) (2020)
EdTechHub.ItemAlsoKnownAs: 2405685:MV5RWXEF

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Sierra Leone) (2018)
EdTechHub.ItemAlsoKnownAs: 2405685:GVAZB6TM

EMIS | Education Management Information System - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)
Library Catalog: mbsse.gov.sl EdTechHub.ItemAlsoKnownAs: 2405685:WDHKTX4J

COVID-19 Education Emergency Response Plan - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)
EdTechHub.ItemAlsoKnownAs: 2405685:XV46GE39

How the Government of Sierra Leone is improving its Education Data Hub - EdTech Hub (EdTech Hub, 2020)
Sierra Leone’s Education Data Hub, is designed to make school-level data more useful in decision making. Nine months into its launch, MBSSE and DSTI were keen to understand who was using the Data Hub, the kinds of decisions it informed, and where improvements were needed to ensure that non-technical users, including policymakers, teachers, parents, and […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707884 2339240:6XDHWICN 2405685:7FQR6GZK 2405685:Y22H6PQD
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

How the Government of Sierra Leone is improving its Education Data Hub (EdTech Hub, 2020)
Sierra Leone’s Education Data Hub is designed to make school-level data more useful in decision making. Nine months into its launch, MBSSE and DSTI were keen to understand who was using the Data Hub, the kinds of decisions it informed, and where improvements were needed to ensure that non-technical users, including policymakers, teachers, parents, and students could access and use…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707888 2405685:E2KWWHCK 2405685:LND4UENT
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
ZenodoArchiveID: 5652063 previousDOI: 10.5281/zenodo.4430545 previousZenodoArchiveID: 4430545 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4430545 10.5281/zenodo.5652063 2339240:94IZR4ET 2339240:TST2YB8H 2405685:3BWKQDYQ 2405685:FEXGB4IJ 2405685:ZGYUEEZQ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Development Projects : Sierra Leone Free Education Project - P167897 - World Bank (World Bank, 2021)
Development Projects : Sierra Leone Free Education Project - P167897
KerkoCite.ItemAlsoKnownAs: 2339240:LFUH26HS 2405685:GZU9SWN9

Education Sector Plan 2018-2020 - Ministry of Education, Science and Technology (Sierra Leone) (2018)
EdTechHub.ItemAlsoKnownAs: 2405685:24PRFKEK

Donor policies in post-war Sierra Leone - Kanyako, Vandy (Journal of Peacebuilding & Development, 2016)
The Sierra Leone peace process following the country's 1991–2002 civil war between the Government of Sierra Leone (GoSL) and the Revolutionary United Front (RUF) benefited immensely from the energetic involvement of an eclectic mix of donors. Traditional inter-governmental financial institutions and relatively new private funding foundations all channelled aid money and technical expertise through various multilateral and bilateral mechanisms for rebuilding the country. Without a doubt Sierra Leone's recovery from the debilitating 11-year war would not have come to pass in the time and manner it did without the robust intervention of such funders. Based on fieldwork conducted in Sierra Leone at the height of the peacebuilding process, this article outlines the role played by international donors in rebuilding post-war Sierra Leone. It posits that understanding the modus operandi of the assorted mix of donor agencies in creating the country's aid architecture is key to grasping the nuances of the Sierra Leone peace process. This is partly because the aid largesse, though well intentioned, was injected into a barely functioning system that lacked a coherent recipient regime. The article concludes that though donors were critical to Sierra Leone's rebuilding efforts, their lack of emphasis on a needs-centred funding mechanism created an inadequate model to address the country's complex post-war reconstruction challenges.
Publisher: SAGE Publications Inc KerkoCite.ItemAlsoKnownAs: 10.1080/15423166.2016.1146035 2339240:EC6LW5LV 2405685:IHKCCGSR

Districts of Teaching Excellence Sierra Leone - Beoku-Betts, Iman; Burgess, Flic (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14794031 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1090 ZenodoArchiveConcept: 14794030
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Strengthening the use of data for decisions on teacher deployment in Sierra Leone: A Geospatial Approach to Workforce Allocation - McBurnie, Chris; Frazer, Madleen Madina; Dube, Gugulethu; Godwin, Katie (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14608646 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1082 ZenodoArchiveConcept: 14608645
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Mapping the education data ecosystem in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652942 10.53832/edtechhub.0068 2339240:GXUF5TA5 2339240:HHY6M835 2339240:SUEMN855 2405685:8S3IIB2B 2405685:EE9QCGHI 2405685:Q7YZW4YW 2405685:RN79UTQY 4656463:GIIQKETU 4656463:Y8LQGZWY
Keywords: _r:AddedByZotZen

Data-Driven Teacher Deployment in Sierra Leone: Practicalities and quantitative analysis of using a matching algorithm in the 2024/25 deployment cycle - Koutecký, Tomáš; Mackintosh, Alasdair; Huti, M; Adam, Taskeen; Godwin, Katie; Frazer, Madleen Madina (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15368231 ZenodoArchiveConcept: 15368230 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1115 2405685:ICRSXHTV 2405685:MUWUTSZS 2486141:MRAYINR3
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

President Bio Commissions Newly Constructed Dr Kadie Sesay Girls Secondary School In Port Loko - SN Radio (2020)
#sierraleone #presidentbio #fatimabio #sierraleoneparliament #sierranetworkproduction #sierranetwork #sierranetworkwanpotshow President Bio Commissions Newly Constructed Dr Kadie Sesay Girls Secondary School In Port Loko. Latest News Website: http://www.blog.snradio.net FaceBook: http://www.facebook.com/SierraNetwork... Youtube: http://www.youtube.com/Salone2Bad Twitter: http://twitter.com/sierra_n_salone Radio: http://SNRadio.net Radio TuneIn App: http://tun.in/sfgyD SoundCould 1: http://www.soundcloud.com/sierra-network SoundCould 2: https://soundcloud.com/sierra-network-sl SoundCould 3: https://soundcloud.com/sierra-network... Contact Us: info@snradio.net Sierra Network For All That Matters Sierra Leone
KerkoCite.ItemAlsoKnownAs: 2405685:PZEXZU6E

Teacher Deployment in Sierra Leone Using a Geographic Information System-Supported Preference Matching Algorithm: A systems analysis - Anonymised for Peer Review (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15368298 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1116 ZenodoArchiveConcept: 15368297
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Improving secondary education in Sierra Leone - De, Sourovi; Durrani, Zara; Khurshid, Ayesha (Oxford Policy Management, 2021)
We are leading the monitoring, evaluation and research delivery of a five year programme to improve secondary education and long term growth in Sierra Leone
KerkoCite.ItemAlsoKnownAs: 2405685:268JSEX2 2486141:EJ4VUWUC

National Education Policy - Ministry of Education, Youth and Sports (Sierra Leone) (2010)
KerkoCite.ItemAlsoKnownAs: 2405685:YLXI3EW2

Shifting Power Dynamics in Education Decision-Making: Investigating the role of a matching algorithm to improve teacher deployment in Sierra Leone - Godwin, Katie; Cameron, Emma; Frazer, Madleen Madina; Dube, Gugulethu; Mackintosh, Alisdair; Koutecký, Tomáš; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15039164 ZenodoArchiveConcept: 15039163 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1103 2405685:IRFH43RX 2405685:SFNCI64Z 2486141:C9Q4ZDTR
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Education in Sierra Leone | Where We Work | Global Partnership for Education - Global Partnership for Education (2007)
Learn more about education in Sierra Leone, view grant information and education data, and explore the results and progress made by the country.
KerkoCite.ItemAlsoKnownAs: 2339240:52XRRPXI 2405685:R9K2NZAQ

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub; Education Commission; Fab Inc. (EdTech Hub, 2022)
ZenodoArchiveID: 5596875 ZenodoArchiveConcept: 5596874 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5896640 10.5281/zenodo.6504993 10.53832/edtechhub.0055 2405685:HT8ZGKAB 2405685:QAH4K4D6 2405685:SE5JPCX2
Keywords: HLR3; _r:AddedByZotZen

Digital School Census in 10 Weeks? How it was done in Sierra Leone - Namit, Kariba; Mai, Thanh Thi (World Bank Blogs, 2019)
Note: This blog is specifically about Sierra Leone’s successful transition to a digital school census but has broader implications for other countries who plan to adopt digital tools at a wider scale to collect data and monitor education and healthcare facilities in their countries. In April of last year, the new Minister of Finance of Sierra Leone approached the World Bank with a strong commitment to prioritize education and an intriguing request.
KerkoCite.ItemAlsoKnownAs: 2405685:BFZ3FTAT 2486141:G289KIHC

Sierra Leone Media Landscape Report - BBC Media Action (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:7N6UW9TG 2405685:644SZI8D

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4896502 10.53832/edtechhub.0066 2339240:9A7P2GEI 2339240:PA2CB3JF 2339240:Q3RLYCNW 2339240:TMHE9JIR 2405685:2CEZ2LKN 2405685:9B56X45X 2405685:FAJLNB8S 2405685:KFTXK9K2 2405685:MPRD5RKR 2405685:PGUR927P 2405685:UKHA4WKY 2486141:A5SQMX8T 4656463:XTGYWNYB
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

School Hits the Airwaves: Sierra Leone Turns to Education Radio as a Response to COVID-19 - World Bank (World Bank, 2021)
Sierra Leone's experience with education radio during the 2014 Ebola outbreak has helped strengthen its radio programming during school closures caused by the COVID-19 pandemic.
KerkoCite.ItemAlsoKnownAs: 2339240:XWD4TCC4 2405685:RLJGATUE

School Hits the Airwaves: Sierra Leone Turns to Education Radio as a Response to COVID-19 - World Bank (The World Bank, 2021)
Sierra Leone's experience with education radio during the 2014 Ebola outbreak has helped strengthen its radio programming during school closures caused by the COVID-19 pandemic.
KerkoCite.ItemAlsoKnownAs: 2339240:TQTHH2MX 2405685:55GPK4S9

Reconstructing education in post-conflict Sierra Leone - Pai, Grace (Security, Education and Development in Contemporary Africa, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:83TRVQZR

Education in Emergencies Endline Evaluation Report – Sierra Leone - Sankoh, Didan; Cowan, Emma (Girls' Education Challenge, UK Aid, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:G2I2A3Y5

Disability in and Around Urban Areas of Sierra Leone - Trani, Jean-Francois; Bah, Osman; Bailey, Nicki; Browne, Joyce; Groce, Nora; Kett, Maria (2017)
KerkoCite.ItemAlsoKnownAs: 2405685:FSQFJ72I

Project Information Document (PID): Sierra Leone Free Education Project (P167897) - World Bank (World Bank Group, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:6FWAUCW5 2405685:XAKZSJBD

Sierra Leone research and knowledge systems: a rapid literature review - Tarawallie, Mamoud Idriss (INASP, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:83QNDI62 2405685:8PAQ6CIE

Using technology to improve the equity of teacher allocation in Sierra Leone: the challenge and a way forward - McBurnie, Chris; Vijil, Alejandra; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6497554 2339240:S7M2CQ4J 2405685:BRY3EXFT 2405685:KAZQRPA7
Keywords: _r:AddedByZotZen

Mitigating COVID-19 impacts and getting education systems up and running again: Lessons from Sierra Leone - Davis, Edward; Berry, Chris (Global Partnership for Education, 2020)
Reflexions on some of the lessons from the Sierra Leone Ebola education response that could be relevant for countries facing shutdowns of their education systems due to the COVID-19 pandemic.
KerkoCite.ItemAlsoKnownAs: 2339240:NIUY9YWK 2405685:CVJKIQ8D

What Matters Most for Teacher Deployment? A case study of teacher preferences in Sierra Leone - McBurnie, Chris; Godwin, Katie; Beoku-Betts, Iman; Bernard-Jones, Lydia; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6530321 10.53832/edtechhub.0095 2129771:G2ULWZXN 2339240:5JUXJ5N6 2339240:F43SL362 2405685:8GN4RWMR 2405685:L4RY53KI 2405685:Q8366KLT 2405685:XNBZSCS7 2486141:Z5CMZLCE
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

Digital 2023: Sierra Leone - Kemp, Simon (DataReportal – Global Digital Insights, 2023)
All the data, insights, and trends you need to help you make sense of the “state of digital” in Sierra Leone in 2023, including detailed statistics for internet use, social media use, and mobile use, as well as user numbers for all the top social platforms.
KerkoCite.ItemAlsoKnownAs: 2339240:RA9DJ5IT 2405685:G5WRLUDH

‘Digital Her’ conference calls time on the gender-gap in Sierra Leone’s digital boom - Forna, Memuna (2024)
The tech sector is growing faster in Africa than any other region. The Digital Her Conference (21 March 2024) asks how can we ensure Sierra Leonean women share fully in the opportunities facilitated by the digital economy as creators, consumers and beneficiaries? Sierra Leone is on the brink of a tr
KerkoCite.ItemAlsoKnownAs: 2339240:J2EGIFZZ 2405685:J59CRUWS

Developing Inclusive Education Policy in Sierra Leone: A Research Informed Approach - Rose, R.; Garner, P.; Farrow, B. (Inclusion, Equity and Access for Individuals with Disabilities., 2019)
https://doi.org/10.100/ 978-981-13-5962-0_21 KerkoCite.ItemAlsoKnownAs: 2405685:AMF2AQAE

Open Data Readiness Assessment: Prepared for the Government of Sierra Leone - Chrzanowski, Pierre; Holm, Jeanne; Manley, Laura; Dodds, Elizabeth; Baker, Rob (World Bank Group; Open Aid Partnership, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:83I8VUFY

RECOVR Sierra Leone: Tracking the Effects of the COVID-19 Pandemic - Warren, Shana; Parkerson, Doug; Collins, Elliott (Innovations for Poverty Action, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:BU58QF73

Republic of Sierra Leone Higher and Tertiary Education Sector Policy Note - World Bank (2013)
KerkoCite.ItemAlsoKnownAs: 2339240:ANFH2ALH 2405685:QAFBTUE9

Education service transformation in Sierra Leone: Where policy meets the people - Sengeh, David (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:Y5AL4GBH 2405685:CL5T3HVF

Successes and challenges of implementing a teacher education project in rural Sierra Leone - Mcdermott, Peter; Allen, Nancy (International Journal of Educational Research, 2015)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijer.2015.02.001 2405685:8F6MKJP5

TVET and community reintegration: exploring the connections in Sierra Leone's DDR process - Paulson, J. (International handbook of education for the changing world of work: bridging academic and vocational learning, 2009)
KerkoCite.ItemAlsoKnownAs: 2405685:SI333Z4W

Devising New Models for School Improvement in Developing Nations: Sierra Leone, a case study - Mason, Miriam Theresa (Durham University, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:55RYBL9Q

Using technology to support teacher continuous professional development in Sierra Leone - Beoku-Betts, Iman; Plaut, Daniel; Tanweer, Rabia; Tanweer, Daniel Plaut and Rabia, Iman Beoku-Betts (EdTech Hub, 2022)
In Sierra Leone, EdTech Hub has been working closely with the TSC and the World Bank over the last 18 months to design a TCPD model that will provide primary school teachers with tools to improve their literacy and numeracy instruction.

A Skills Gap Analysis for Private Sector Development in Sierra Leone 2012 Economic Sector Work - Mannah, Emmanuel; Ngadi Gibril, Yvonne (2012)
KerkoCite.ItemAlsoKnownAs: 2405685:RFM2MVCL

Sierra Leone | Education and Literacy Statistics - UNESCO (2020)
...
Last Modified: 2017-04-12 Library Catalog: uis.unesco.org KerkoCite.ItemAlsoKnownAs: 2405685:Y6JYY6Q6

GSMA Mobile Connectivity Index | Sierra Leone - GSMA (2018)
The GSMA Mobile Connectivity Index is a global mobile connectivity and digital economy guide covering 150 countries and 7 sub-regions
Library Catalog: www.mobileconnectivityindex.com EdTechHub.ItemAlsoKnownAs: 2405685:AGNKXIPC

Sierra Leone Multiple Indicator Cluster Survey - UNICEF (2017)
KerkoCite.ItemAlsoKnownAs: 2405685:6T7FE548

COL in the Commonwealth: Sierra Leone - Commonwealth of Learning (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:I3SFDGVA

Using examination and learning assessment data to uncover foundational skill gaps in Sierra Leone’s secondary schools - Waistell, Daniel; De, Sourovi; Ofori Owusu, Diana; Allen, Reg; Sanni, Kayode; Dupigny, Albert (Education technology and data science for inclusive systems, 2019)
KerkoCite.ItemAlsoKnownAs: 2405685:J8IWHLVQ
Keywords: ⛔ No DOI found

The Athens of West Africa: A History of International Education at Fourah Bay College, Freetown, Sierra Leone - Paracka, Daniel J. (2006)
This book is about Fourah Bay College (FBC) and its role as an institution of higher learning in both its African and international context. The study traces the College's development through periods of missionary education (1816-1876), colonial education (1876-1938), and development education (1938-2001).
KerkoCite.ItemAlsoKnownAs: 2339240:993UCWCL 2405685:3CTGQYRP

Sierra Leone: Transforming the Country through Innovation - O'Connor, Shane; Zurutuza, Naroa (UNICEF, 2019)
Library Catalog: www.unicef.org KerkoCite.ItemAlsoKnownAs: 2405685:XYSCRRC4

Project Information Document: Sierra Leone Free Education Project - World Bank (2019)
EdTechHub.ItemAlsoKnownAs: 2405685:GIC5MV46

Revitalizing Education Development in Sierra Leone (REDISL) Project - World Bank (2014)
KerkoCite.ItemAlsoKnownAs: 2405685:8ISYUKP9

It takes a village to raise a teacher: the Learning Assistant programme in Sierra Leone - Crisp, Martin; Wolfenden, Freda (2017)
KerkoCite.ItemAlsoKnownAs: 2405685:I76Z2SKV

A Comprehensive Situation Analysis of Teachers and the Teaching Profession in Sierra Leone: Final report presented to the Teaching Service Commission - Wright, Dr. Cream (Global Partnership for Education; World Bank, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:9VRVIUE6 2405685:UU3R28HB

How Sierra Leone is betting on data to fight the impact of climate change on schools - Momoh, A; Atherton, Paul (Global Partnership for Education, 2022)
Data can significantly improve decision-making and allow for prioritizing interventions to benefit the most vulnerable populations. That’s why the ministry of Education in Sierra Leone is working with Fab Inc. to develop a web-based data tool that helps estimate and prioritize where new schools are really needed.
KerkoCite.ItemAlsoKnownAs: 2405685:AVDJP4T3 4042040:AJHHQGBH

Ebola, Education And Innovation In Sierra Leone - Berry, Chris (DFID bloggers, 2015)
KerkoCite.ItemAlsoKnownAs: 2339240:Y4SENBBT 2405685:CYLG6GK7 2405685:DD7BMIBU
Keywords: ___working_potential_duplicate

How can Sierra Leone’s education response after Ebola help with the COVID-19 response? - Bangay, Colin (The Education and Development Forum (UKFIET), 2020)
This blog is written by Colin Bangay, Senior Education Adviser, Department for International Development (DFID). It aims to look at some practical and sensible lessons from the education response in Sierra Leone during the Ebola outbreak, to help others as they face closures of education systems. This blog was originally published on the Global Partnership […]
KerkoCite.ItemAlsoKnownAs: 2339240:D5Q8A77B 2405685:PK7UUFGK

Introduction of an EdTech intervention to support learning of foundational skills in Sierra Leone: policy, teacher, and community perspectives - Lurvink, Anne-Fleur; Pitchford, Nicola J. (Frontiers in Education, 2023)
Background: Like many other countries, Sierra Leone faces significant challenges with primary education resulting in many children leaving primary school without acquiring basic foundational skills. To address these challenges, an educational technology (EdTech) intervention was implemented in 20 primary schools located in two marginalized districts in Sierra Leone. While this EdTech intervention has been shown to raise learning outcomes, little is known about the impacts on the broader education ecosystem. This paper investigates how this EdTech intervention might address some the challenges faced with primary education in Sierra Leone, by examining policy, teacher, and community perspectives. Method: A mixed methods approach was employed which included a policy mapping exercise, a survey of teachers training needs in supporting the development of foundational skills with grade 1 learners, an interview with teachers after they had delivered the EdTech intervention to garner their perceptions and experiences of using the technology in their class, and focus groups with teachers and other community members to gain insights into how the EdTech intervention had been received. Results: Findings from the policy mapping exercise and quantitative data from the survey of teacher training needs were triangulated with qualitative data from the interviews and focus groups. Four key themes emerged relating to the effective and sustained use of this EdTech intervention to support the acquisition of foundational skills by primary school children in Sierra Leone: (1) the need for continued teacher professional development, (2) the use of English as the language of instruction, (3) access to the technology by children with special educational needs and disabilities (SEND), and (4) the importance of active community engagement in supporting the intervention. Discussion: Collectively, results indicated that the EdTech intervention employed in this study aligned well to the education policy in Sierra Leone. Enhanced teacher training is needed, especially in using English as the language of instruction, and continued community engagement is essential for scaling the intervention effectively and ensuring that all children, including those with SEND, access the technology at primary school. These results have implications for other EdTech intervention deployed in resource-poor settings to enhance learning of foundational skills.
KerkoCite.ItemAlsoKnownAs: 2339240:J83HRBE6 2405685:BTDXQFJ9

Final Evaluation of the Project: Increasing Access, Retention and Performance in Primary Education: Implemented by Child to Child & the Pikin-To-Pikin Movement Kailahun District, Sierra Leone, 2011-2016 - Institute for Development (2016)
KerkoCite.ItemAlsoKnownAs: 2339240:3E624NH3 2405685:5LVXNGJZ 2405685:CRQUMLFF

‘Tich Mi Ar Tich Dem’: Designing a low-cost and scalable teacher professional development in Sierra Leone - Walker, Hannah; Tegha, Ghislaine; Lurvink, Anne-Fleur; McBurnie, Chris (Open Development & Education, 2022)
Reading Time: 4 minutes Over the past two decades, Sierra Leone has faced a series of shocks: a civil war, landslides, Ebola, and the COVID-19 pandemic. These shocks have aggravated the learning crisis that the country’s education system faces—and dramatically increased the pressure on teachers to deliver high-quality support to children. In this context, the Ministry of Basic and […]
KerkoCite.ItemAlsoKnownAs: 2339240:75HR9DSN 2405685:9TLXNWMJ 2405685:FBHX876D

Sierra Leone and Liberia: Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (World Bank; OECD; Harvard Global Education Innovation Initiative; HundrED, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:BRFU9F86 2405685:93KUAPNF 2405685:9APBFG2P 2405685:CXIWGJLQ 2405685:STZ89LHX 2534378:UQINHJH2

Education Needs Assessment Report - Sierra Leone - Plan International (2016)
KerkoCite.ItemAlsoKnownAs: 2405685:FPBLY982 2486141:T8M7TVMD

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
KerkoCite.ItemAlsoKnownAs: 2405685:AN5GA9QR
Keywords: ___working_potential_duplicate

2021 Annual School Census Final Report - Ministry of Basic and Senior Secondary Education, Sierra Leone (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:M7XYZTWF 2405685:C7C3BM9Z

Republic of Sierra Leone Settlement Extents - GRID3 (Center for International Earth Science Information Network (CIESIN), Columbia University and Novel-T, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:HAJEN8QZ 2405685:M3AVWB8Q

Are LLMs useful in the poorest schools? TheTeacher.AI in Sierra Leone - Choi, Jun Ho; Garrod, Oliver; Atherton, Paul; Joyce-Gibbons, Andrew; Mason-Sesay, Miriam; Björkegren, Daniel (arXiv, 2024)
Education systems in developing countries have few resources to serve large, poor populations. How might generative AI integrate into classrooms? This paper introduces an AI chatbot designed to assist teachers in Sierra Leone with professional development to improve their instruction. We describe initial findings from early implementation across 122 schools and 193 teachers, and analyze its use with qualitative observations and by analyzing queries. Teachers use the system for lesson planning, classroom management, and subject matter. Usage is sustained over the school year, and a subset of teachers use the system more regularly. We draw conclusions from these findings about how generative AI systems can be integrated into school systems in low income countries.
arXiv:2310.02982 [cs] version: 2 KerkoCite.ItemAlsoKnownAs: 10.48550/arXiv.2310.02982 2405685:WTRDUD84
Keywords: Computer Science - Computers and Society

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:X5MR76ZW 2405685:29U93GQF

Technology and Teacher Professional Development (TPD): the Process and Content of Microlearning in a School-Based Integrated In-Service Teacher Education (INSET) Project - Junaid, Muhammad Ibn; Ogange, Betty; Allela, Melisa (Commonwealth of Learning (COL), 2019)
Continuing teacher professional development for all teachers across the entire school system poses a challenge in many contexts, especially in developing countries. Teachers from schools located in remote rural areas usually have fewer professional development opportunities due to the lack of accessibility either to their schools or to professional development resources. On-site school-based professional development is a viable option if innovative design is adapted to generate microlearning resources that teachers can easily access and share. This paper reports on a technology enabled school-based integrated INSET project coordinated by the Freetown Teachers College (FTC) in 12 junior secondary schools (JSS) in Sierra Leone under the COL’s Teacher Futures Programme. The project represents an innovation in TPD and is different from the general type of face-to-face and exclusively paper-based in-service teacher training programme common in Sierra Leone. Under the new project a multimodal approach is used where the FTC mentors and the communities of learners (JSS teachers) are presented with both print and microlearning resources and also provided access to an eLearning platform and the use of mobile phones as the main vehicles of delivery. Microlearning is an emergent learning strategy known for its quick response in bridging skills and knowledge gaps. In the context of the INSET Project, it involves a weekly dose of pedagogical content knowledge and skills, including modelling of classroom best practices which teachers can adapt and use. The project design and methods are briefly described, but the main focus of the paper is on the microlearning component of this project and discusses the use of mobile technology in the delivery and implementation of TPD in the 12 project schools. The emphasis is on the methodological and management challenges that arise in creating and nurturing communities of practice (CoPs) in a school-based setting and how these are addressed by the various schools involved.
KerkoCite.ItemAlsoKnownAs: 2405685:AALEIRC2

Teachers and Teaching in Sierra Leone - The World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:346EVURZ 2405685:I5ZDCPFW

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10604329 ZenodoArchiveConcept: 10604328 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10080685 10.53832/edtechhub.1005 2405685:GXMUGXHE 2405685:RK44C9BZ
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

2019 Annual Schools Census Report And Statistical Abstract - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:MJH7EBNP 2405685:VM4EWGLU

Benefit Incidence Analysis of the Education Sector in Sierra Leone - Ministry of Finance (Government of Sierra Leone, 2023)
DOWNLOAD
KerkoCite.ItemAlsoKnownAs: 2339240:8GYX9MM4 2405685:WQW66Q4H

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7335773 ZenodoArchiveConcept: 7335772 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7299806 10.5281/zenodo.7335773 10.53832/edtechhub.0165 2339240:LJTXPKUD 2405685:4NSU75DR 2405685:ABK6ZFI8 2405685:PFKAMFI6
Keywords: _r:AddedByZotZen

FQSE – Free Quality School Education - Ministry of Basic and Senior Secondary Education Sierra Leone (Ministry of Basic and Senior Secondary Education Sierra Leone, Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:XL83AVZI 2405685:7NLKWES7

Sierra Leone Teaching Service Commission Act - Government of Sierra Leone (2011)
KerkoCite.ItemAlsoKnownAs: 2339240:XVKYXQ4E 2405685:D8ZBENA6

About Us | Teaching Service Commission - Sierra Leone - Teaching Service Commission (Government of Sierra Leone, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:46QDPXDM 2405685:E9YPU485

Sierra Leone Education Sector Plan 2022-2026 - Ministry of Basic and Senior Secondary Education; Ministry of Technical & Higher Education (Government of Sierra Leone, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:JLYG52CA 2405685:MYV4GHKW

National Strategy for Out-of-School Children in Sierra Leone - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:F39I9PTD 2405685:BLKSJRLU

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
ZenodoArchiveID: 4556932 PreviousDOI: 10.5281/zenodo.4477141 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948149 10.5281/ZENODO.4556932 10.5281/zenodo.4477141 10.5281/zenodo.4556932 2259720:DSXFK6JB 2339240:4JRWSL6I 2339240:8YVF7D5N 2339240:EPCMUN8C 2339240:FKFII8IK 2339240:H8YNQIY9 2339240:IJJ6TY76 2339240:QBDJ6U43 2339240:YIAFCN9T 2405685:5GBRDVHP 2405685:65UPSCK3 2405685:67BFM4C5 2405685:6CG6479A 2405685:DM6JSS9K 2405685:P8NUYK3M 2405685:PZHGV2XR 2405685:QBYZW7N2 2405685:RBUXXHAD 2405685:VHGNZV9N 2405685:X8BFH2K5 2405685:YMWE6FR6
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Basic and Senior Secondary Education Act, 2023 - Government of Sierra Leone (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:X4WE79XI 2405685:JWZZ6UGY

EMIS – MBSSE - Government of Sierra Leone (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:HKHF8XA6 2405685:BWCAJFI4 4656463:QV6UP6K3

Exploring donor-driven skills development as a channel of continued aid dependency - Harris, Jamelia (Third World Quarterly, 2023)
Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.1080/01436597.2023.2178889 2339240:WTZ26BCQ 2405685:3CVCLUXZ
Keywords: NGOs; Sierra Leone; Skills development; aid; dependency

Education Sector Analysis: Assessing the enabling environment for gender equality - Republic of Sierra Leone; UNICEF; IIEP-UNESCO Dakar (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:3EEMJ5QE 2405685:YIC6SIQI

A rapid scan of the EdTech landscape in 11 countries - Taddese, Abeba (EdTech Hub, 2020)
By Abeba Taddese We have just produced rapid scans of the EdTech landscape in 11 countries: Ghana, Jordan, Kenya, Liberia, Nigeria, Pakistan, Rwanda, Senegal, Sierra Leone, Tanzania, and Zimbabwe. The scans are based primarily on desk research and offer a glimpse into the countries’ EdTech ecosystems. They examine enabling factors for EdTech from a holistic systems perspective but are by…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707872 2405685:9EPB5ZXS
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

Education in Africa: What Are We Learning? - Evans, David; Acosta, Amina Mendez (2020)
Countries across Africa continue to face major challenges in education. In this review, we examine 145 recent empirical studies (from 2014 onward) on how to increase access to and improve the quality of education across the continent, specifically examining how these studies update previous research findings. We find that 64 percent of the studies evaluate government implemented programs, 36 percent include detailed cost analysis, and 35 percent evaluate multiple treatment arms. We identify several areas where new studies provide rigorous evidence on topics that do not figure prominently in earlier evidence syntheses. New evidence shows promising impacts of structured pedagogy interventions (which typically provide a variety of inputs, such as lesson plans and training for teachers together with new materials for students) and of mother tongue instruction interventions, as well as from a range of teacher programs, including both remunerative (pay-for-performance of various designs) and non-remunerative (coaching and certain types of training) programs. School feeding delivers gains in both access and learning. New studies also show long-term positive impacts of eliminating school fees for primary school and positive impacts of eliminating fees in secondary school. Education technology interventions have decidedly mixed impacts, as do school grant programs and programs providing individual learning inputs (e.g., uniforms or textbooks).
KerkoCite.ItemAlsoKnownAs: 2339240:I9QLRLND 2405685:BUVF2SY4
Keywords: ⛔ No DOI found

The Education Act, 2004 - Kabbah, President Alhaji Ahmad Tejan (2004)
KerkoCite.ItemAlsoKnownAs: 2339240:X2LEVVUF 2405685:TI5ZIK8J

Keynote Address by His Excellency President Julius Maada Bio on the theme of: "Education for Development" at the launch of the Free Quality School Education Programme - Maada Bio, Julius (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:5TSMLUKK 2405685:FW7MT9FE

What makes a good classroom? New UIS data on school conditions - UNESCO (UNESCO, 2019)
New data from the UNESCO Institute for Statistics (UIS) reveal serious disparities in the schooling conditions facing children and teachers – from access to electricity, clean drinking water and single sex-toilets to Internet access and computers. Classroom conditions are key in providing a quality education for all. For children who struggle to enrol in school, for example due to poverty or discrimination on the grounds of gender or disability, poor school conditions can further undermine their chances of a quality education. What are the new data looking at?
KerkoCite.ItemAlsoKnownAs: 2339240:4DRK8RBZ 2405685:PT5I7FT5

The Tertiary Education Commission Act - Kabbah, President Alhaji Ahmad Tejan (2001)
KerkoCite.ItemAlsoKnownAs: 2405685:URKBLF52

The National Council for Technical , Vocational and other Academic Awards Act - Kabbah, President Alhaji Ahmad Tejan (2001)
KerkoCite.ItemAlsoKnownAs: 2405685:M3MZ2L84

The Polytechnics Act - Kabbah, President Alhaji Ahmad Tejan (2001)
KerkoCite.ItemAlsoKnownAs: 2405685:HMGAWLHC

The Universities Act - Kabbah, President Alhaji Ahmad Tejan (2005)
KerkoCite.ItemAlsoKnownAs: 2405685:6FAZDP79

Continental Education Strategy For Africa (2016 – 2025) - African Union (2016)
KerkoCite.ItemAlsoKnownAs: 2405685:EH4P26FW

Education for sustainable development in Africa: a critique of regional agendas - Tikly, Leon (Asia Pacific Education Review, 2019)
Education is often perceived in policy agendas as playing a transformative role in realising sustainable development and the SDGs on the continent. The assumption is based, however, on an insufficiently critical understanding of the historical role of education in supporting unsustainable development. The article provides a critical account of the relationship between education policy and sustainable development in Africa as an aspect of the postcolonial condition, i.e. as an aspect of the colonial legacy and of Africa’s position in relation to contemporary processes of globalisation. It is argued that if education is to play a transformative role in relation to sustainable development then education policy needs to be fundamentally re-oriented and harnessed to wider processes of economic, cultural and political transformation in the interests of social and environmental justice.
KerkoCite.ItemAlsoKnownAs: 10.1007/s12564-019-09600-5 2405685:UUXGULFV

Rwanda Vision 2020 - Ministry of Finance and Economic Planning (Republic of Rwanda, 2000)
KerkoCite.ItemAlsoKnownAs: 2405685:2BFX8SK3

Kenya Vision 2030: A Globally Competitive and Prosperous Kenya - Government of Kenya (Republic of Kenya, 2007)
KerkoCite.ItemAlsoKnownAs: 2405685:IPSRUIML

Ethiopia Growth and Transformation Plan II (GTP II) | Green Growth Knowledge Platform - Ethiopia National Planning Commission (Federal Democratic Republic of Ethiopia, 2016)
KerkoCite.ItemAlsoKnownAs: 2405685:XG2MRXIK

DSTI Education Data Hub - DSTI (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:IYNCGEPI 2405685:88RPBVJU

Education Innovation Challenge - Reflection & Learning Summit Report - DSTI (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:M28U3MQY 2405685:YNNFWZLA

Reimagining Education for Continuous Learning and Teaching - Sengeh, Hon Minister David Moinina; Team, MBSSE Delivery; Team, Hon Minister David Moinina Sengeh and MBSSE Delivery (EdTech Hub, 2021)
EdTech Hub has partnered with the Ministry of Basic and Senior Secondary Education in Sierra Leone to increase the use of evidence in decisions around EdTech. Click to read more.
KerkoCite.ItemAlsoKnownAs: 2339240:6JKPNDHR 2405685:SQ7GPXQJ

Radical inclusion means teaching children in a language they understand - Bah, Chernor (Brookings, 2022)
Chenor Bah examines how Sierra Leone is trying to incorporate radical inclusion within the national education system by ensuring children are taught their mother-tongue for the first three to five years of schooling.
KerkoCite.ItemAlsoKnownAs: 2339240:FND65Y2H 2405685:7G5GS3YN

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
ZenodoArchiveID: 5652007 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652007 2405685:KZ6FTNMC
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

Sierra Leone Series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health - McBurnie, Chris; Swaray, Abdulai; Kamara, Bai (EdTech Hub, 2021)
ZenodoArchiveID: 5652005 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652005 2405685:RT5H8XNG
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

From algorithm outputs to classroom impact: A conversation with Marian Abu, director of teacher management at the Teaching Service Commission - Frazer, Madleen Madina (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14266292 ZenodoArchiveConcept: 14266291 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1080 2405685:AUFN9TP4 2405685:WIB4DE6R 2486141:TQ3SZHVM
Keywords: _EdTechHub_Output; _r:AddedByMyEducationEvidence

UNICEF Sierra Leone - UNICEF (2022)
Learn how we are supporting children across the country to reach their full potential.
KerkoCite.ItemAlsoKnownAs: 2339240:GFGZWUTT 2405685:LX8UD5MZ

Sierra Leone – Giga - GIGA; UNICEF (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:5D9RW69Z 2405685:7YBMSLS4

Sierra Leone population 2020 - WorldPop (2018)
RF-based gridded population distribution datasets produced in the framework of the Global Project - Funded by The Bill and Melinda Gates Foundation (OPP1134076)
KerkoCite.ItemAlsoKnownAs: 10.5258/SOTON/WP00645 2339240:2AJ3LMLD 2405685:92787LQS
Keywords: Population distribution; Population; Dasymetric disaggregation

Transforming Teacher Deployment: Lessons from a matching algorithm tool - Frazer, Madleen Madina; Adam, Taskeen; Godwin, Katie; Mackintosh, Alisdair; Haßler, Björn (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15368169 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1114 ZenodoArchiveConcept: 15368168
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Sierra Leone | Technology | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:G8958J9Q 2405685:F5K8RR2H

EAGER Scenario Model – Sierra Leone - Cochran, Mikaela (The International Rescue Committee, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:CXF88QEI 2339240:UWF4RMSZ 2405685:UEIPLTJ9 2405685:UGYV6DSA

Sierra Leone Free Education Project - World Bank (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:MSP6V8I2 2405685:REKP5PJD

Education | Sierra Leone | Save the Children - Save the Children (2024)
KerkoCite.ItemAlsoKnownAs: 2339240:ZTLL99IS 2405685:Z5K7YXLN

Open Data Readiness Assessment: Sierra Leone - World Bank (2015)
KerkoCite.ItemAlsoKnownAs: 2339240:GHD8WBJM 2405685:5GLY6KEA

Education Workforce Management in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Commission, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:28FQ3DS8 2405685:QEWLRFDX

Sierra Leone Education Attendance Monitoring System - Teaching Service Commission (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:CLIEEVEU 2405685:XV88ZYD7

Country-level research review: Sierra Leone - Kallon Kelly, Christiana; Koomar, Saalim; Kreimeia, Adam; McBurnie, Chris; Mitchell, Joel; Myers, Christina (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:746WTJF3 2405685:HNVAP5QB
Keywords: dode_eth-src-eth

Teacher Management Policy for Sierra Leone - Teaching Service Commission (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:ILC2GGZX 2129771:XQMFH5JU 2339240:5QZ2N3GQ 2339240:QSY3I4ZA 2405685:M6F97ARN 2405685:RFT2PNDX 4556019:49UIZ3SU
Keywords: _C:Sierra Leone SLE

Government of Sierra Leone Education Data Hub - Directorate of Science, Technology and Innovation (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:8BAXTEYI 2405685:46EQS5JF

Education Workforce Spatial Analysis in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Commission, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:XF3I7T7Y 2339240:Q42KZNBD 2339240:V7GZZAMR 2405685:2HRVB9KF 2405685:4AGUYJZJ 2405685:B5LNLGZL 2405685:FS263PV6 4042040:ZQNXW7RV 4556019:S386467K
Keywords: _yl:a; ⛔ No DOI found

Sierra Leone - Multiple Indicator Cluster Survey 2017 - World Bank (2017)
KerkoCite.ItemAlsoKnownAs: 2339240:693W742X 2405685:4ULW3LMX

Cost-Effective Approaches to Improve Global Learning - Global Education Evidence Advisory Panel (2023)
KerkoCite.ItemAlsoKnownAs: 2405685:URLC9S2L 2486141:9A53JU2Q

Education for Development - Maada Bio, Julius (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:KL7FDUU7

Proportion of schools with access to basic facilities, all schools - UNESCO (2018)
EdTechHub.ItemAlsoKnownAs: 2405685:ZV8MELAV

SALCAB | Home - SALCAB (2020)
EdTechHub.ItemAlsoKnownAs: 2405685:7LEIDSTB

Mobile Learning Lab Evaluation & Analysis - 60 Million Girls (60 million girls, 2018)
Library Catalog: 60millionsdefilles.org EdTechHub.ItemAlsoKnownAs: 2405685:ZPG2W382

Education Workforce Recruitment and Matching in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Workforce Initiative, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:2JR2FXVK 2339240:8YVNU64V 2405685:KZBP674C 2405685:Q8T7NH3C 2405685:S38LF89P 2486141:BQG3BPG7 4556019:S8AD6237
Keywords: _yl:b; ⛔ No DOI found

Individuals using the Internet (% of population) - Sierra Leone - International Telecommunication Union (World Bank Open Data, 2022)
Free and open access to global development data
KerkoCite.ItemAlsoKnownAs: 2339240:SAP2T6U2 2405685:EJFTAQ95

Education Workforce Supply and Needs in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (the Education Commission; Fab Inc., 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:2KB28MDX 2339240:LYKK26AE 2405685:52ZGRDGR 2405685:8MIWRFD2 2405685:QMGGDQ4G
Keywords: ⛔ No DOI found

EdTech, Learning and Equity: The EdTech Hub Research Portfolio - Haßler, Björn; Wagner, Dan; Outhwaite, Laura (EdTechHub, 2023)
ZenodoArchiveID: 10079721 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1000 ZenodoArchiveConcept: 10079720
Keywords: _internal; _r:AddedByMyEducationEvidence

Sierra Leone teacher & school MIS developments: Sierra Leone Education Attendance Monitoring System (SLEAMS) and Teacher Records Management (TRM) system - Graham, Hannah (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:KB3DUZXF 2405685:5NEC3AR4

Teaching and Testing by Phone in a Pandemic - Crawfurd, Lee; Evans, David K.; Hares, Susannah; Sandefur, Justin (Center for Global Development, 2021)
How did children learn while schools were closed during 2020 due to the COVID-19 pandemic? In this paper we evaluate the effectiveness of live tutoring calls from teachers, using a randomized controlled trial with 4,399 primary school students in Sierra Leone.
KerkoCite.ItemAlsoKnownAs: 2339240:474HKXRJ 2339240:FTSVR76S 2339240:GAPVTT3N 2339240:K9KUNITI 2405685:5RJW9S5N 2405685:7AP7H3CG 2405685:DTZ6IE85 2405685:H3J9AJ2Z 2405685:KW3QGYS5 2534379:ZTWPMXUG
Keywords: ___working_potential_duplicate

Wi De Ya, One Tablet Per School, Sierra Leone - CGA Technologies (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:YP3PPJRH 2405685:X9WGBYV4

Sierra Leone Secondary Education Improvement Programme II (SSEIP II) - Foreign, Commonwealth Development Office (GOV.UK, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:KKMBX7JV 2405685:U74G9ACW

Leh Wi Learn - Sierra Leone Secondary Education Improvement Programme - Foreign, Commonwealth Development Office (GOV.UK, 2024)
KerkoCite.ItemAlsoKnownAs: 2339240:X4QX7MSL 2405685:LUH7MFXZ

Sierra Leone joins Elon Musk's Starlink satellite service - Komminoth, Leo (African Business, 2023)
The country now joins Nigeria, Mozambique, Rwanda, and Mauritius as African nations connected to Elon Musk's Starlink.
KerkoCite.ItemAlsoKnownAs: 2339240:NAF4JVME 2405685:UEE8UWYC

Leh Wi Learn - Sierra Leone Secondary Education Improvement Programme - DFID (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:9PJP3ZYU

Sierra Leone and Liberia: Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:XVKVLR6R 2405685:QV99MR4Q

Systems-Level Analysis of Education Service Delivery in Sierra Leone - Education Partnerships Group (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:8354FEB6 2486141:PFQ2N79R

Sierra Leone: Economic Development Documents-National Development Plan, 2019-23 - International Monetary Fund (IMF, African Department, 2019)
ISBN: 9781498324960 ISSN: 1934-7685 Issue: 218 Publisher: INTERNATIONAL MONETARY FUND Volume: 2019 KerkoCite.ItemAlsoKnownAs: 10.5089/9781498324960.002.A001 2339240:6RP4BCNR 2405685:LICLRGV3

Innovative Education Workforce Analysis for More Equitable Education: Sierra Leone - Education Workforce Initiative (Education Commission, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:XCXZB356 2405685:67AH3BDQ

Independent Reporting Mechanism (IRM): Sierra Leone Design Report 2019–2021 - Field, Tracey-Lynn (Open Government Partnership, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:8XF8TYGA 2405685:YMJMKLLJ

Sierra Leone Education Attendance Monitoring System (SLEAMS) Final Technical Report - Graham, Hannah; Kawa, Muniru; Lee, Philip; Malyon, Stephanie; Hayward, Harry; Conteh, Sheriff; Chandia, Gloria (Charlie Goldsmiths Associates, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:M68LGCE7 2405685:FTT9TD2Y

West African Senior School Certificate Examination: Sierra Leone Results Analysis - Ministry of Basic and Secondary Education (2022)
KerkoCite.ItemAlsoKnownAs: 2339240:2WY3SC9N 2405685:YKA8Y8DM

Automated teller machines (ATMs) (per 100,000 adults) - Sierra Leone - World Bank (2012)
KerkoCite.ItemAlsoKnownAs: 2129771:EERHMIDA 2405685:IECJPUES 4556019:QB8DZSFF

Teachers and the Teaching Profession in Sierra Leone: A comprehensive situation analysis - Wright, Cream (Teaching Service Commission, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:BPP6QJJT 2405685:K3L9HBBP 2405685:S8XYIRCN 2486141:4XFKHYLJ 2601447:KDYSFZB9

A longitudinal study of learning, progression, and personal growth in Sierra Leone - Johnson, David; Hsieh, Jenny (University of Oxford, 2019)
EdTechHub.ItemAlsoKnownAs: 2405685:A2EVGSWW

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:ZNYWJ9PF 2405685:7HSIXMSV
Keywords: ___working_potential_duplicate

Sierra Leone Education Attendance Monitoring System (SLEAMS) Pilot Phase: Inception Report - Kawa, Muniru; Graham, Hannah; Lee, Philip; Murray, Tobias; Malyon, Stephanie (Charlie Goldsmiths Associates, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:EPHMUJLL 2405685:F8XG7GDF

Teachers and Teaching in Sierra Leone : Teacher Quality and Management Study - World Bank (2021)
KerkoCite.ItemAlsoKnownAs: 2129771:X6L76LFL 2405685:4KSNK63S 4556019:BHQLRIPR
Keywords: _C:Sierra Leone

Incidence of HIV, all (per 1,000 uninfected population) - Sierra Leone | Data - World Bank (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:RSRU6YLV 2405685:RFVHGC9Z 4556019:CI8YJ5UC

Guidance Note on Education Data Mapping in Sub-Saharan Africa: Moving from theory to practice - Selwaness, Irene; Adam, Taskeen; Lawson, Laté; Heady, Lucy (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6339212 10.53832/edtechhub.0096 2339240:VJZWBP65 2405685:6JLQ7UC6 2405685:KQUDWCXC
Keywords: _r:AddedByZotZen

Republic of Sierra Leone: Education sector analysis: assessing the enabling environment for gender equality - UNICEF (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:A6RXK3ZC 2405685:UG524M3N

The permanent input hypothesis : the case of textbooks and (no) student learning in Sierra Leone - Sabarwal, Shwetlena; Evans, David K.; Marshak, Anastasia (Washington, DC : World Bank, Education Global Practice Group & Africa Region, Office of the Chief Economist, 2014)
KerkoCite.ItemAlsoKnownAs: 2405685:QFBK2Z4L

Education continuity during the Coronavirus crisis: Sierra Leone and Liberia Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (Rising Academy Network, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:YUCXSRDK 2405685:U7GMEU2U

Getting girls back into school: strategies for successfully re-enrolling girls in Ghana and Sierra Leone - Belfield, Sophie; Mathur, Meenu; Caine, Ellie (FCDO - GEC, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:GMMKRGS8 2405685:79GPUNG4

Live tutoring calls did not improve learning during the COVID-19 pandemic in Sierra Leone - Crawfurd, Lee; Evans, David K.; Hares, Susannah; Sandefur, Justin (Journal of Development Economics, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jdeveco.2023.103114 2405685:D8BHBGK9

Sierra Leone Case Study: Review of Technology-Based Interventions to Address Child Marriage and Female Genital Mutilation - Data-Pop Alliance; United Nations Population Fund; UNICEF (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:CEHUC88T 2405685:S24H3HV7

Mapping education data in sub-Saharan Africa: Our experience from the Unlocking Data campaign and Sierra Leone - Unlocking Data (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:HAKTFJKU 2405685:YPE9D2W3

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:JUGDD7MG 2405685:CYTW2JQW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Recovering from school closures in Sierra Leone: Status of pupil learning outcomes in junior and senior secondary schools - Leh Wi Lan (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:TVYLJS4I 2405685:IUJU327A

Incidence of malaria (per 1,000 population at risk) - Sierra Leone, Sub-Saharan Africa (excluding high income) | Data - World Bank (2018)
KerkoCite.ItemAlsoKnownAs: 2129771:6RCWKTSF 2405685:7HILUDQR 4556019:XR5GKQEB

How Can EMIS be Designed and Implemented in Ways That Make Them Used and Useful? - Adam, Taskeen; Mitchell, Joel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at education management information systems (EMIS). EMIS are pivotal in educational administration, facilitating the digitisation of processes and data to enable informed decision-making. However, persistent challenges impede their effectiveness. We examine why it is vital to consider how EMIS are designed and implemented, particularly with regard to the needs and contexts of low- and middle-income countries (LMICs). We consider constraints in technical capacity, limited funding, and insufficient user engagement. We identify concrete, evidence-based recommendations for how to make EMIS useful and used more frequently based on current and recent research. To enhance EMIS efficacy, there is a need to underscore utility and usability, ensuring the collection of pertinent data and user-friendly interfaces. Furthermore, the social implications of EMIS data on individuals and communities must be considered in order to meet their needs. We also explore areas for further consideration and include lists of resources relevant to EMIS and questions and solutions to consider. Keywords: education management information systems (EMIS); low- and middle-income countries (LMICs); user-centred design; evidence-based decision-making; EdTech; educational administration. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694602 ZenodoArchiveConcept: 10694601 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10080734 10.53832/edtechhub.1015
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Tech plus teachers: Did one-on-one phone tutorials help kids learn better during school closures in Sierra Leone? - Crawfurd, L; Evans, D; Guiterrez Bernal, M; Hares, S; Sam-Kpakra, R; Sandefur, J; Shojo, M (2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5Z8RBH2S 2405685:TF3CV7CH

Toward a holistic approach to EdTech effectiveness: Lessons from Covid-19 research in Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone - Nicolai, Susan; Jordan, Katy; Adam, Taskeen; Kaye, Tom; Myers, Christina (International Journal of Educational Development, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2023.102841 2405685:EFV98PTB

A Comprehensive Situation Analysis of Teachers and the Teaching Profession in Sierra Leone: Final report presented to the Teaching Service Commission - Teaching Service Commission (Global Partnership for Education, 2018)
KerkoCite.ItemAlsoKnownAs: 2405685:CFRE6D4Q

No Teacher is an Island: A case study on the enablers and barriers for effective school-based teacher professional development in Sierra Leone - Lurvink, Anne-Fleur; Bangura, Zainab; Fortune, Alhaji; George, Alex H.; Godwin, Katie; Mason-Sesay, Miriam; Moseray, David; Tholley, Ibrahim; Turay, Emmanuel B.; Haßler, Björn; Open Development & Education (OpenDevEd, 2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.0284 2405685:JDHJV2U4

Cost Effective Approaches to Improve Global Learning What Does Recent Evidence Tell Us Are Smart Buys for Improving Learning in Low-and-Middle-Income Countries - Global Education Evidence Advisory Panel (World Bank; FCDO; Building Evidence in Education, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:IL3G2LER 2339240:IQT7LI8P 2405685:9YMXHH74 2405685:CN86U6UQ 2405685:LX2STYUZ

Understanding the Barriers and enablers of Effective Communities of Practice in Sierra Leone Through a Collaboration Between Dubai Cares and Open Development and Education - Lurvink, Anne-Fleur (Open Development & Education, 2019)

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3878423 previousshortDOI: 10/ghgk6n previousshortDOI: 10/ghgk6n previousDOI: 10.5281/zenodo.3878423 previousshortDOI: 10/ghgk6n EdTechHub.Source: 2405685:DS66UGW4 EdTechHub.Source: <this> shortDOI: 10/ghgk6n KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3878423 10.53832/edtechhub.0019 10/ghgk6n 2129771:GKIQY5RP 2339240:29BIZJM5 2339240:WSA5X76N 2405685:4Z5W36SI 2405685:DS66UGW4 2405685:IS587WTH
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Ed-Tech landscape and challenges in Sub-Saharan Africa - Adeniran, Adedeji; Adedeji, Abdulfatai; Nwosu, Emmanuel; Nwugo, Emmanuel; Nnamani, Great (Southern Voice, 2023)
This study examines the adoption of education technology (ed-tech) in primary and secondary education in 10 sub-Saharan African countries: Nigeria, South Africa, Sierra Leone, Uganda, Kenya, Tanzania, Cameroon, Benin, Malawi, and Senegal. The study assesses the development and implementation of ed-tech policies and programmes in the region, exploring how far ed-tech has advanced learning outcomes, improved access, and reduced education inequalities within and between countries in sub-Saharan Africa.
KerkoCite.ItemAlsoKnownAs: 2339240:RUBC88S3 2405685:TE8RFCSM

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
10.5281/zenodo.4913283 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0048 10.53832/edtechhub.0049 2339240:487NSL2N 2339240:96WXZFG3 2339240:BXUFCQ98 2339240:QUJFSUDE 2405685:4NFT3P7H 2405685:MZSKKWUZ 2405685:NVIUXYC6 2405685:PIXT9J66 2405685:RL5CTZU3 2405685:U8GMZZ48 2486141:7MQA6V3G 4656463:6378IJC5 4656463:TD3MYCHJ
Keywords: _EdTechHub_Output; _MELA_seen

How Can Implementers Apply Digital Personalised Learning in Schools? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at digital personalised learning (DPL), a promising EdTech approach to improving learning outcomes, and consider how to implement this approach in school settings. We draw on work from EdTech Hub and other prominent researchers to first unpack the ‘basics’ of DPL implementation. These include the importance of teaching at the right level as a driver of DPL’s impact, and how DPL tools are applied in schools as supplementary learning and / or integrated into existing curricula. We also consider some of DPL’s technical requirements and achievements in improving learning outcomes. We then explore emerging insights about effective DPL implementation in schools, including the role of teachers as facilitators, the evidence behind student-device ratios, and the importance of coordinating DPL implementation with broader education system actors. Lastly, we look at areas that require further research, noting issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to DPL application in education systems. Keywords: digital personalised learning; DPL; implementation research; teaching at the right level; learning outcomes; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10616734 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1008 ZenodoArchiveConcept: 10616733
Keywords: _r:AddedByMyEducationEvidence

How to Guide: Delivering High-Quality Radio Learning - Rising Academies; EdTech Hub (2021)
ZenodoArchiveID: 4486906 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4486906 2339240:NTGE2FPC 2405685:DU497D8A 2405685:HCV5X9YJ
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3865298 previousshortDOI: 10/ghgk6p previousshortDOI: 10/ghgk6p previousDOI: 10.5281/zenodo.3865298 shortDOI: 10/ghgk6p KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 10.53832/edtechhub.0020 10/ghgk6p 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:CEADG684 2405685:H52W8E9M 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:AD3D9NRM 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:SNBG3VHT 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?” As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Library Catalog: edtechhub.org Section: general shortDOI: 10/ghgk6c KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3690149 10/ghgk6c 2339240:6LUYX6ZR 2339240:AS8A9UGV 2405685:CV2HG6CJ 2405685:FI72KCVG 2405685:JTA347FP 2405685:N2YMVN4S 2405685:TEVH3TNS
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
previousshortDOI: 10/gg8hqq previousshortDOI: 10/gg8hqq previousDOI: 10.5281/zenodo.3804380 previousshortDOI: 10/gg8hqq EdTechHub.Source: 2405685:UXQG7GRG EdTechHub.Source: <this> shortDOI: 10/gg8hqq KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3804380 10.53832/edtechhub.0014 10/gg8hqq 2129771:X82WTVD8 2339240:4X8SH6RY 2339240:MB7JNNNV 2339240:PGI4RZNE 2405685:59LAMBXS 2405685:88UWQMW9 2405685:BG5DGC4G 2405685:GQDN2E5P 2405685:SYLGY9MM 2405685:UXQG7GRG
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

Where do teachers go, and where do they stay? - Lurvink, Anne-Fleur; Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alasdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn; Godwin, Katie; Godwin, Patricia Espinoza-Revollo, Yusuf Ali, Oliver Garrod, Paul Atherton, Alasdair Mackintosh, Ana Ramirez, Iman Beoku-Betts, Björn Haßler and Katie, Anne-Fleur Lurvink (EdTech Hub, 2023)
In Sierra Leone, a government payroll position is tied to the teacher, not the school, meaning teachers can change schools once they go on the payroll. This leads to certain schools being chronically understaffed. It also suggests that deploying teachers to rural and understaffed schools (or putting teachers already there on payroll) might not tackle high pupil-to-qualified-teacher ratios in the longer term. Investigating the school-to-school movement of payroll teachers can help us understand where teachers go after they go on the payroll and how long they stay in a given school. We also looked at overall movement nationally to identify areas of the country that are outliers in terms of high and low retention of teachers.
KerkoCite.ItemAlsoKnownAs: 2405685:LC8X4TCC

Effectiveness of Multimodal Microlearning for In-Service Teacher Training - Allela, Melisa Achoko; Ogange, Betty Obura; Junaid, Muhammad Ibn; Charles, Prince Brainard (Journal of Learning for Development, 2020)
To meet the growing demand for continuing professional development of practising teachers, the integrated in-service teacher training (INSET) programme aims at making permanent improvements on the quality of teaching and learning for Junior Secondary School (JSS) Teachers in Sierra Leone. Within this context, a toolkit for School-Based Teacher Development was created and microlearning identified as an ideal mode to deliver the toolkit content. In this paper, we present the design considerations that informed this decision as well as challenges and lessons learned from the first implementation of the INSET project for junior secondary school teachers in Sierra Leone. A multimodal approach was considered and implemented to mitigate Internet access challenges and to expand learning opportunities. These include a mobile app version of the Toolkit, offline access to microlearning resources on the TeacherFutures platform via the Moodle mobile app, a mobile app version of one INSET module, an e-portfolio to be used by participants in sharing their learnings as demonstrated and practised during a face-to-face roll-out seminar, and finally, WhatsApp groups in which different schools engaged in discussions based on the questions on the Toolkit. Preliminary findings indicate a strong preference among participants for the use of WhatsApp as the main channel of communication within the communities of practice; and very limited use of the main e-learning Moodle platform and e-Portfolio. This necessitates a need to critically evaluate the effectiveness of the design of a multimodal approach for delivering microlearning content. From this, we seek to establish a set of design considerations, capacity building and technical support issues derived from analysis of data emerging from the ongoing project rollout. This will inform future integration of Microlearning resources in the teacher training project.
Publisher: Commonwealth of Learning KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v7i3.387 2339240:98GSBC3X 2405685:Z794TZUM
Keywords: Barriers; Communities of Practice; Electronic Learning; Foreign Countries; Inservice Teacher Education; Integrated Learning Systems; Internet; Multimedia Materials; Portfolios (Background Materials); Professional Continuing Education; Professional Development; Program Effectiveness; Secondary School Teachers; Social Media; Synchronous Communication; Teacher Collaboration; Teacher Competencies; Workshops

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7371460 ZenodoArchiveConcept: 7371459 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7371460 10.5281/zenodo.7473922 10.5281/zenodo.7500121 10.53832/edtechhub.0151 2339240:BE2J66WG 2405685:BBAPFKW4 2405685:JHWKC6F4 2405685:P833K7KC 2405685:YLS6YQ3U
Keywords: _r:AddedByZotZen

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13255974 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1052 ZenodoArchiveConcept: 13255973
Keywords: _r:AddedByMyEducationEvidence

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
ZenodoArchiveID: 5651983 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5651983 2339240:C67KNIJR 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2339240:W7FD9YT3 2405685:26VNTFQU 2405685:94AITL9D 2405685:DQ5URLSY 2405685:GT33JADA 2405685:VJ488Z7L zotzenLib.CopiedFrom: 2339240:C67KNIJR
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341501 ZenodoArchiveConcept: 7341500 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341501 10.53832/edtechhub.0138 2405685:E7C9MN3V
Keywords: _r:AddedByZotZen

Data Access and Protection Laws in Pakistan: A technical review - Halim, Waqas; Upadhyay, Arjun; Coflan, Caitlin (EdTech Hub, 2022)
The advancement of technologies has supported an exponential rise in the collection and use of data. Data, when used appropriately, can support better decision-making and inform innovation. Data has value to entrepreneurs and innovators who seek to design products that respond to user needs. However, the widespread collection and use of data have also spawned concerns about individual rights and data privacy. Issues related to collection, usage, dissemination, and access to data have also come to the forefront. To address these concerns, many countries across the globe have introduced data protection laws. This policy brief identifies and analyses global best practices in data protection and data access. It is developed in response to an inquiry related to data and research in the education sector, specifically in Pakistan. The brief explores the potential practical challenges in the enforcement and implementation of global good practices in the context of the data protection environment in Pakistan; it proposes a set of key recommendations for the Government of Pakistan, provincial governments, development partners, and other education-related ministries and public departments. Keywords: Data protection (laws), good practices, data access, privacy rights, children's data, sensitive data, data-driven policy, data integration, third-party data sharing, open data, data security, data governance, encryption An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6621244 10.53832/edtechhub.0098 2405685:GV4MKFZH
Keywords: _r:AddedByZotZen

Annual School Census Report - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ELC26RCU 2405685:2GVLUELP 2405685:6I3545CN 2405685:UP66E9KW 2486141:U5LTFSMK
Keywords: auto_merged

2022 Annual School Census Report - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:38CKEZFQ 2405685:QGJ7924G

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5120788 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5120788 10.5281/zenodo.5142473 2405685:3C8VWLJP 2405685:772S7Z4R 2405685:CW2FHVT8
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
previousshortDOI: 10/ghgng4 previousDOI: 10.5281/zenodo.3885806 EdTechHub.Source: 2405685:CMS6HPI8 EdTechHub.Source: <this> shortDOI: 10/ghgng4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3875138 10.5281/zenodo.3885806 10.53832/edtechhub.0042 10/ghgng4 2129771:FCNVWJUI 2129771:VJXKA7AN 2339240:FEGWVFS3 2339240:FJ5LQ7QK 2405685:79LULMUU 2405685:BTWBKYN7 2405685:CMS6HPI8 2405685:HLCYI98H 2405685:RV5RNCII
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Les Technologies De L’enseignement Et Le Covid-19 - 10 Choses À Savoir - EdTech Hub Team (2021)
ZenodoArchiveID: 4709702 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709702 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:VJ488Z7L
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Using Interactive Radio Instruction to Mitigate the Educational Impact of Covid-19: A curated resource list - McBurnie, Chris (EdTech Hub, 2020)
Interactive Radio Instruction (IRI) is a distance education tool that enables educators to use radio broadcasts to direct active learning in the home. This curated list of resources aims to inform and support the use of IRI to mitigate the educational impact of Covid-19.
previousshortDOI: 10/ghgng5 previousDOI: 10.5281/zenodo.3762228 EdTechHub.Copy: 2129771:QQWNSYJR EdTechHub.Copy: 2129771:QQWNSYJR shortDOI: 10/ghgng5 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3762228 10.53832/edtechhub.0022 10/ghgng5 2129771:QQWNSYJR 2339240:45F2G56T 2405685:3MKIMX34 2405685:A3T2DQ4D 2405685:WB97BS9V
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Overview of emerging country-level response to providing educational continuity under COVID-19: What are the lessons learned from supporting education for marginalised girls that could be relevant for EdTech responses to COVID-19 in lower- and middle-income countries? - Naylor, Ruth; Gorgen, Kristine (EdTech Hub, 2020)
ZenodoArchiveID: 4706059 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706059 2339240:3HJRFVNR 2339240:3VR6UC7F 2339240:9U79NYYD 2339240:NCZSLKX5 2339240:UEWQXHSF 2339240:YFCV9UXA 2339240:YMYNESML 2405685:9NJI87R8 2405685:B54L7JGC 2405685:C6QUC3Z7 2405685:D9SU8CEK 2405685:LK4JMG78 2405685:PW66MNDR 2405685:SLJSKY8J 2405685:VSAZQYD7 2405685:Z3XYMJZN
Keywords: COV:COVID and reopening of schools; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
ZenodoArchiveID: 5652135 previousDOI: 10.5281/zenodo.3906041 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906041 10.5281/zenodo.5652135 2339240:546TH9C9 2339240:E5AXYSMF 2339240:RKVKV84H 2405685:4ER9WB55 2405685:7JSP4PFC 2405685:DMSLLEQV 2405685:HZ5X5A4W 2405685:V44Z75Z3 2405685:VVB3BRE5
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Guidance on Pre-Assessment for Establishing E-Learning Centres - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5813529 10.53832/edtechhub.0084 2405685:DPWSAA9Z
Keywords: _r:AddedByZotZen

Session 3: How can I develop an aligned and actionable EdTech strategy - Wyss, Natalie; Mbugua, Wanjiku; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341466 ZenodoArchiveConcept: 7341465 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341466 10.53832/edtechhub.0137 2405685:VVT2BI9M
Keywords: _r:AddedByZotZen

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
ZenodoArchiveID: 5652036 Dates: 13-11-2020 — Actualizado el 09-01-2021 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652036 10.6018/red.453621 2405685:2BIQKP9C 2405685:IVHRNTQ7 2405685:L7Y5JD68 2405685:ZXQZ3FVV
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

The Economic Lives of Young Women in the Time of Ebola: Lessons from an Empowerment Program - Bandiera, Oriana; Buehren, Niklas; Goldstein, Markus; Rasul, Imran; Smurra, Andrea (World Bank, 2018)
We evaluate an intervention to raise young women’s economic empowerment in Sierra Leone, where women frequently experience sexual violence and face multiple economic disadvantages. The intervention provides them with a protective space (a club) where they can …nd support, receive information on health/reproductive issues and vocational training. Unexpectedly, the post-baseline period coincided with the 2014 Ebola outbreak. Our analysis leverages quasi-random across-village variation in the severity of Ebola-related disruption, and random assignment of villages to the intervention to document the impact of the Ebola outbreak on the economic lives of 4 700 women tracked over the crisis, and any ameliorating role played by the intervention. In highly disrupted control villages, the crisis leads younger girls to spend signi…cantly more time with men, out-of-wedlock pregnancies rise, and as a result, they experience a persistent 16pp drop in school enrolment post-crisis. These adverse e¤ects are almost entirely reversed in treated villages because the intervention enables young girls to allocate time away from men, preventing out-of-wedlock pregnancies and enabling them to re-enrol in school post-crisis. In treated villages, the unavailability of young women leads some older girls to use transactional sex as a coping strategy. The intervention causes them to increase contraceptive use so this does not translate into higher fertility. Our analysis pinpoints the mechanisms through which the severity of the aggregate shock impacts the economic lives of young women, and shows how interventions in times of crisis can interlink outcomes across younger and older cohorts. JEL Classi…cation: I25, J13, J24.
shortDOI: 10/ghgngq KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-8760 10.1596/31219 10/ghgngn 10/ghgngq 2339240:P9QQ2FKF 2405685:2TEE6A8C 2405685:BA7ISGH3
Keywords: ___working_potential_duplicate

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Government of Sierra Leone; UNICEF, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:843DCCS6 2405685:HZ89SJYF

Consequences of school closure on access to education: lessons from the 2013–2016 Ebola pandemic - Smith, William C. (International Review of Education, 2021)
The COVID-19 pandemic has seen an unprecedented shutdown of society. Among the various safety measures taken, much attention has been given to school closure as a non-pharmaceutical mitigation tool to curb the spread of the disease through ensuring “social” (physical) distancing. Nearly 1.725 billion children in over 95% of countries worldwide have been affected by school closures implemented in April 2020 as the virus continued to spread. In the field of education, policymakers’ attention has been directed at keeping students on board through remote learning and addressing the immediate needs of schools upon reopening. The study presented in this article focuses on who remains absent after schools resume. Using publicly available survey data from the USAID Demographic Health Surveys Program and the UNICEF Multiple Indicator Cluster Survey from before and after the 2013–2016 Ebola pandemic in Guinea and Sierra Leone in West Africa, the author examined changes in school enrolment and dropout patterns, with targeted consideration given to traditionally marginalised groups. At the time, schools closed for between seven to nine months in the two countries; this length and intensity makes this Ebola pandemic the only health crisis in the recent past to come close to the pandemic-related school closures experienced in 2020. The author’s findings suggest that post-Ebola, youth in the poorest households saw the largest increase in school dropout. Exceeding expected pre-Ebola dropout rates, an additional 17,400 of the poorest secondary-age youth were out of school. This evidence is important for minimising the likely post-COVID-19 expansion in inequality. The author’s findings point to the need for sustainable planning that looks beyond the reopening of educational institutions to include comprehensive financial support packages for groups most likely to be affected.
KerkoCite.ItemAlsoKnownAs: 10.1007/s11159-021-09900-2 2339240:JKCDRWKL 2405685:JFZ4ET3L

EdTech Policy Rapid Scan for Sub-Saharan Africa - Flam, Rebekka; Oyedele, Oluwatomisin (EdTech Hub, 2025)
This rapid scan presents a curated list of EdTech policies in sub-Saharan Africa, compiled in response to a request from the World Bank. Based on desk research from mid-2024, it highlights that most policies predate COVID-19, with few new ones emerging post-2020. Many countries lack dedicated EdTech policies, instead relying on broader ICT or education strategies. Common themes include digital infrastructure, distance learning, and teacher training, while gaps remain in support for marginalised learners. The report provides an overview of existing policies, while the highlighted trends offer insights for future policy development. Keywords: EdTech policy; education policy; sub-Saharan Africa; EdTech governance; digital learning; digital infrastructure An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14749795 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1089 ZenodoArchiveConcept: 14749794
Keywords: _r:AddedByMyEducationEvidence

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
ZenodoArchiveID: 5652066 previousZenodoArchiveID: 3885606 previousshortDOI: 10/ghgnfw previousDOI: 10.5281/zenodo.3885606 EdTechHub.Copy: 2129771:VAP9K6BW EdTechHub.Copy: 2129771:VAP9K6BW shortDOI: 10/ghgnfw KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3885606 10.5281/zenodo.3885606 10.53832/edtechhub.0026 10/ghgnfw 2129771:IK97VLY8 2129771:MXTVUGAA 2129771:VAP9K6BW 2339240:2ZVLRPTQ 2339240:7PXTZ2FQ 2339240:ZE9V9N4R 2405685:8IJT433J 2405685:9TKV7H6E 2405685:BBLQFJKE 2405685:IDL75DHT 2405685:WMUEC2ZV 2405685:Z2VNN7ER
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5512134 2405685:8M6GXINE 2405685:JGTWVQI4
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5604677 10.5281/zenodo.5761966 10.53832/edtechhub.0069 2405685:CPP3A2WM 2405685:DM8N3E8E 2405685:PXUQJZTH
Keywords: Helpdesk Response; _r:AddedByZotZen

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5495857 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5495857 10.53832/edtechhub.0045 2339240:23D7YNSM 2339240:ESWRJBRS 2339240:PVDW8BXZ 2405685:69W2G8TJ 2405685:6KFAB5ML 2405685:UYDUMKBR 2405685:V9Y8MUDX 2405685:W8DB96IE
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

2019 Annual School Census Report - Ministry of Basic and Senior Secondary Education (Ministry of Basic and Senior Secondary Education, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:99GBVUWP 2339240:NBI2YGW4 2405685:PF3NKF32 2405685:QNZEXSV3 2405685:SK6ZDI63 2486141:IVGKRIEH

تكنولوجيا التعليم وجائحة كوفيد 19 - .10 أشياء يجب معرفتها - EdTech Hub Team (2021)
ZenodoArchiveID: 4709700 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709700 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:VJ488Z7L
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6924683 10.53832/edtechhub.0102 2339240:LDWT8LYC 2405685:JPXVGB3A 2405685:MNMTIMGA 2405685:Q9J54HFA
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6980271 ZenodoArchiveConcept: 6980270 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6980271 10.53832/edtechhub.0109 2405685:HPWRQP7M
Keywords: _r:AddedByZotZen

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4917252 10.5281/zenodo.4917252 2339240:G2X4SJI9 2339240:MUSPGK9F 2339240:MVU3QIHM 2339240:NQF22P32 2405685:B2ABXUCR 2405685:D6PWMC4I 2405685:HW7NU96L 2405685:JWIHBL5M 2405685:PXBXCZ29 2405685:YHC5ZPU8
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

10 principles to consider when introducing ICTs into remote, low-income educational environments - Trucano, Michael (World Bank Blogs, 2013)
there must be an I, a C, and a T here somewhere ... There are, broadly speaking, two strands of concurrent thinking that dominate discussions around the use of new technologies in education around the world. At one end of the continuum, talk is dominated by words like 'transformation'. The ...
Library Catalog: blogs.worldbank.org KerkoCite.ItemAlsoKnownAs: 2339240:5I5XNP44 2339240:7ENMXVAZ 2339240:7TDXW2WT 2339240:M7NFMPY5 2405685:23SM2GHY 2405685:2KLF59UJ 2405685:4QHLLY7H 2405685:BJSJWEMM 2405685:EJG6JBSL 2405685:EY7WAUHY 2405685:MDR3XLXP 2405685:N584ISNZ 2405685:RCHYAVL3 2405685:SVDWLWHS 2405685:XED3H9S7 4042040:MXSNKXZ5 4656463:P4BDEDD3 4656463:YXDWWIE2

Policy Guidelines on School Approvals - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:ABRJGSC5 2405685:WMH7EW6P

National Policy on Radical Inclusion in Schools - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:5UGTMJFK 2405685:K5LB484Z

National Policy on Radical Inclusion in Schools Implementation Plan 2021-2026 - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:ZIUJRRAJ 2405685:J2YDQU25

Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15792725 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1125 ZenodoArchiveConcept: 15792724
Keywords: _r:AddedByMyEducationEvidence

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
ZenodoArchiveID: 4749652 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749652 2339240:B796SJQD 2339240:DI5RWJ4S 2405685:6MJNV8GC 2405685:TFLZLVTW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Transforming Education Service Delivery Through Evidence-Informed Policy and Practice - The Ministry of Basic and Senior Secondary Education (MBSSE) (The Ministry of Basic and Senior Secondary Education (MBSSE), 2021)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4550561 2129771:49ZQ5QHA 2405685:F2VBE6CR

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4776960 2339240:JASYN9AV 2339240:URJVJP9H 2405685:7QBDH9I4 2405685:MXMPWAA2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15366685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1113 ZenodoArchiveConcept: 15366684
Keywords: _r:AddedByMyEducationEvidence

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0115 2339240:3KZX9ARU 2405685:BBQE9QUM 2405685:UUDK52LQ 2405685:YB52PCMQ
Keywords: ⛔ No INSPIRE recid found

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Building an Acceptable Use Policy - Tanweer, Rabia; Wyss, Natalie (EdTech Hub, 2023)
Acceptable use policies (AUPs) aim to define how digital and technological tools and services (both devices and ICT services) should be used in or by education systems and actors. These policies address the rights, privileges, responsibilities, and ramifications associated with the use of technology in education spaces and for educational purposes. In doing so, AUPs attempt to promote good practice and responsible, safe use of the internet and digital technologies. This brief uses global examples of AUP policies and guidance on the development of AUPs to outline best practices and key considerations for the development of AUPs. Keywords: EdTech usage; acceptable use policy; tablets; laptops; desktop computers; EdTech hardware; EdTech software. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7754059 ZenodoArchiveConcept: 7754058 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521858 10.5281/zenodo.7754059 10.53832/edtechhub.0161 2405685:6E2WK46K
Keywords: _r:AddedByZotZen

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
previousPreviousDOI: 10.5281/zenodo.4557508 PreviousDOI: 10.5281/zenodo.4557508 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4557508 10.53832/edtechhub.0002 2129771:BKEP82PS 2339240:KF364I3I 2405685:2CKWI7RR 2405685:ESKCB3SZ 2405685:SRFG8S6C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR
Keywords: auto_merged

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5576416 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5576416 10.53832/edtechhub.0052 2339240:282R466B 2339240:EQWZQPHA 2405685:2B2RMIDY 2405685:AEQDZV3T 2405685:DX6WMTLN 2405685:NNN9EZ7J
Keywords: _r:AddedByZotZen

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
ZenodoArchiveID: 4557015 PrevoousDOI: 10.5281/zenodo.4502122 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4502122 10.5281/zenodo.4557015 2339240:6Z8Q4VYT 2339240:KCTXJNS6 2405685:HZRHPNI5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
previousshortDOI: 10/ghgk6v previousDOI: 10.5281/zenodo.3346903 EdTechHub.Source: 2405685:3BG5X7VG EdTechHub.Source: <this> shortDOI: 10/ghgk6v KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3346903 10.53832/edtechhub.0017 10/ghgk6v 2129771:FLGEYF22 2339240:SZ4GSDD6 2405685:3BG5X7VG
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

Mission and Vision - Ministry of Technical & Higher Education (Ministry of Technical & Higher Education Republic of Sierra Leone, Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:PM4PUYXJ 2405685:LI99LYJA

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4966322 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4966322 10.53832/edtechhub.0115 10.53832/edtechhub.0116 2405685:8HKCSIRC
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:2FHWWFA3 2339240:322MPSF7 2339240:8BXMXD7P 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:SILWX2ZS 2339240:WEEFFITS 2339240:XHVAUXYZ 2405685:347U73VH 2405685:4LA8N3BT 2405685:8F46F44X 2405685:94F2MYRK 2405685:BHLDEAHG 2405685:CQXKYRLY 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R2YGTN82 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
ZenodoArchiveID: 4749654 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749654 2405685:39XPD5EM 2405685:QZ2FJC4E
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
ZenodoArchiveID: 4768571 previousDOI: 10.5281/zenodo.4277895 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4277895 10.5281/zenodo.4768571 2339240:5M4KPPAH 2339240:MQLLLDAJ 2405685:S7JARBXV 2405685:T2HBLDU6 2405685:TE7A3D6X
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
ZenodoArchiveID: 4556938 PreviousDOI: 10.5281/zenodo.4058181 PreviousDOI: 10.5281/zenodo.4477015 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4058181 10.5281/ZENODO.4556938 10.5281/zenodo.4477015 10.5281/zenodo.4556938 2339240:8QFLYEYK 2339240:ATYZFQ8R 2339240:CUBEJEWS 2339240:LCAUL9ZC 2339240:NISQD6JT 2339240:T2Z992XW 2339240:XMQV9Y56 2339240:YGQCMSDP 2405685:2GE8ESCR 2405685:4G8DT7ZB 2405685:4JM6QWPH 2405685:5NMCR3LL 2405685:EQVI8NMV 2405685:IU849P3E 2405685:MMTHETFR 2405685:PY3CXCH9 2405685:QSD5LYSF 2405685:XHBPFYVC 2405685:Z7P9NRWJ
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5721401 10.53832/edtechhub.0070 2339240:CHJR9D5G 2339240:RFJZSHMG 2405685:FE3VBQQW 2405685:NFXKD34I 2405685:PU8D6GXN 2405685:SY9TIAMH
Keywords: _r:AddedByZotZen

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7906889 ZenodoArchiveConcept: 7906888 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7906875 10.5281/zenodo.7906889 10.53832/edtechhub.0163 2339240:2LWVXYCV 2405685:4CB23ZC6 2405685:AG764A26 2405685:VWJXTPI8
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

About the Ministry – Ministry of Communication, Technology & Innovation - Ministry of Communication, Technology & Innovation (Ministry of Communication, Technology & Innovation, Government of Sierra Leone, 2024)
KerkoCite.ItemAlsoKnownAs: 2339240:W2WW8I6D 2405685:4ZS3MLSW

Statement from the Minister - Ministry of Technical & Higher Education (Ministry of Technical & Higher Education, Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:QIYCJQ6B 2405685:7G2FJMLB

Flagship Projects - Directorate of Science, Technology & Innovation (Directorate of Science, Technology & Innovation, Government of Sierra Leone, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:94U79QP8 2405685:ZEJRQ8R7

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
ZenodoArchiveID: 4140412 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4140412 2129771:9X3BTTLU 2339240:9PYYNK6J 2405685:ISTFVCA7 2405685:NS927T5K
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech to Support Blended Learning in Mozambique: A curated list of EdTech interventions - Flam, Rebekka; Ramesh Vasudevan, Sharanya; Coutrim, Erica (EdTech Hub, 2024)
This document was produced in response to a request from the UNICEF Mozambique country office submitted to the EdTech Hub Helpdesk in November 2023. The UNICEF team requested a curated list of blended learning approaches and resources that are relevant to the Mozambique context, with a special focus on resources that are implemented or sourced from the Eastern and Southern Africa region. In response, the EdTech Hub Helpdesk has created this report to provide contextual and background information on the blended learning landscape in Eastern and Southern Africa, with a specific focus on Mozambique, along with a list of resources on blended learning. Keywords: blended learning; hybrid learning; Africa; Mozambique An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10599846 ZenodoArchiveConcept: 10599845 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1004 2339240:VBH94XQQ 2405685:DJRV7KZW
Keywords: _r:AddedByMyEducationEvidence

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5611467 10.53832/edtechhub.0064 2339240:E542Q29N 2405685:2A5NQEV8 2405685:6JC7RU69 2405685:T3ZQ74QF
Keywords: _r:AddedByZotZen

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
ZenodoArchiveID: 5652092 previousDOI: 10.5281/zenodo.4140104 previousZenodoArchiveID: 4140104 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4140104 10.5281/zenodo.4140104 10.5281/zenodo.4140104; 10.5281/zenodo.5652092 2339240:2K6FG2CF 2339240:2XJTN3MP 2339240:3TNWACL9 2339240:942WVA7N 2339240:DN7NQV5Y 2339240:LKQW3A8S 2339240:MDTPARWA 2339240:PNTVB7PY 2339240:U3838PXA 2339240:XIE9NJ3S 2405685:5DNJGPNU 2405685:BA3K6CK8 2405685:BLRKEEAU 2405685:CCZW4ARW 2405685:DAFBBJ3F 2405685:DP9HJGLT 2405685:HRT8E6US 2405685:RVIEHPP5 2405685:XUVA9827 2405685:Z6UIK8CZ 2405685:ZITF5IDK 2534379:FDZIF5DH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (Education Commission, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
shortDOI: 10/ghgk64 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3983877 10/ghgk64 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:7SUZMICK 2339240:BGZYE7EH 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:88MADQ2R 2405685:FPPVW2ZG 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6 2405685:WVC3S4C8
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
shortDOI: 10/ghgk63 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4118177 10/ghgk63 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:BGZYE7EH 2339240:FTULJL3H 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:2G7TFTEB 2405685:F2B8T3ZP 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (EdTech Hub, 2020)
EdTech Hub participated in a question and answer session in May 2020 for policymakers in The Maldives and Sri Lanka. The session focused on the challenges and issues in designing effective distance education programmes during the Covid-19 pandemic. This document provides answers to a list of 13 questions received from stakeholders.
ZenodoArchiveID: 5652128 previousZenodoArchiveID: 3885817 previousshortDOI: 10/ghgngv previousshortDOI: 10/ghgngv previousDOI: 10.5281/zenodo.3885817 previousshortDOI: 10/ghgngv EdTechHub.Source: 2405685:HE2Q6Z8Y EdTechHub.Source: <this> shortDOI: 10/ghgngv KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3885817 10.53832/edtechhub.0018 10/ghgngv 2129771:YC82FCEP 2339240:TND87RAP 2405685:HE2Q6Z8Y 2405685:SRU74BP6
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:5NZNS3QV 2339240:CPK8K89T 2339240:RBDWQM22 2405685:6RBRWKND 2405685:I9KB2AZ7 2405685:KV39KIGX 2405685:NVJN7R29 2405685:YD8GYZDT
Keywords: ⛔ No DOI found

About the MBSSE - Ministry of Basic and Senior Secondary Education (Ministry of Basic and Senior Secondary Education, Government of Sierra Leone, 2024)
KerkoCite.ItemAlsoKnownAs: 2339240:BILIZ8KM 2405685:28TCKZ8D

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 4: Content curation - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fourth of five reports on the development of a proof of concept for the Hub and describes our observations during content curation. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803092 10.53832/edtechhub.0078 2405685:9VKXVKGI
Keywords: _r:AddedByZotZen

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524840 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524840 10.53832/edtechhub.0047 2339240:LSC89UVX 2339240:RIE9TWUK 2339240:SI398B6V 2405685:54BCQ23M 2405685:6NNCFPHE 2405685:77NJVUB6 2405685:HUY7VUM6 2405685:VTQDT65R 2405685:WFDCC7KZ 2534378:BQ8BJBGF
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 PreviousDOI: 10.5281/zenodo.4557484 KerkoCite.ItemAlsoKnownAs: 2129771:HT9D5C8E 2129771:HT9D5C8E 10.5281/zenodo.4557484 10.53832/edtechhub.0001 2129771:HT9D5C8E 2339240:HPLKGS4I 2339240:RQGHJZV7 2339240:S3YSSL2W 2405685:K2FX6IVZ 2405685:T6YJ3L5G 2405685:TD2ASC4G 2405685:ZNQCJ5R7
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5849102 10.53832/edtechhub.0071 2339240:5YT7LKSS 2405685:6FN5VTP7 2405685:8UMQILZ9 2405685:GMA7II34 2405685:WEG87IDU
Keywords: _r:AddedByZotZen

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
EdTechHub.Source: 2129771:WMYNLNVK KerkoCite.ItemAlsoKnownAs: 2129771:GIJXZ5UC 2129771:WMYNLNVK 2129771:ZQ6YQRSI 2405685:TI6VMAWR 2405685:TRRZUHFS 2486141:HFLTMIZV
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651935 previousDOI: 10.5281/zenodo.4923094 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4923094 10.5281/zenodo.5651935 2339240:6ELB8P84 2339240:HZ3EBZ29 2405685:79JJ5T29 2405685:P8IAN448 2405685:RU8ET9S2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
EdTechHub.Source: 2129771:9IYKEUKJ shortDOI: 10/f8f6mc KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12123 10/f8f6mc 2129771:6YGVDBXS 2129771:9IYKEUKJ 2129771:BFWTG2BG 2129771:HX6DBG7W 2317526:3V7LV2NP 2339240:C6LDZSDW 2339240:GNBA7ZJI 2339240:WPK23R37 2339240:YYGY6J8F 2405685:7552P2EL 2405685:9I6F956M 2405685:J6HBWCZL 2405685:SZ2DB7K2 503888:U6FRZHMB
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets